Method for producing sulfide-based inorganic solid electrolyte material, method for producing phosphorus sulfide composition, method for evaluating phosphorus sulfide composition, and phosphorus sulfide composition

By using a specific X-ray distributed phosphorus sulfide composition for mechanical treatment and vitrification, a sulfide-based inorganic solid electrolyte material with improved lithium ion conductivity was prepared, which solved the problem of degradation of lithium ion conductivity in the prior art and achieved a stable improvement in battery performance.

CN120202516APending Publication Date: 2025-06-24FURUKAWA COMPANY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380078176.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-11-11
Filing Date
2023-11-01
Publication Date
2025-06-24

AI Technical Summary

Technical Problem

The existing sulfide-based inorganic solid electrolyte materials have problems of degradation in lithium ion conductivity, resulting in unstable battery performance.

Method used

By using a specific X-ray distributed phosphorus sulfide composition as a raw material, mechanical treatment and vitrification treatment, a sulfide-based inorganic solid electrolyte material with improved lithium ion conductivity was prepared.

Benefits of technology

It has achieved stable improvement of lithium-ion conductivity of lithium-ion batteries and enhanced performance stability and safety of the batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120202516A_ABST
    Figure CN120202516A_ABST
Patent Text Reader

Abstract

The present invention provides a method for producing a sulfide-based inorganic solid electrolyte material, the present invention relates to a method for producing a sulfide-based inorganic solid electrolyte material, which comprises a step for obtaining a glass-state sulfide-based inorganic solid electrolyte material by mechanically treating a starting material composition of a sulfide-based inorganic solid electrolyte material containing a lithium sulfide and a phosphorus sulfide composition to chemically react the components and vitrify the components at the same time. The phosphorus sulfide composition has three or more peaks in the range of 2 [theta] = 22.5-24.5 DEG (inclusive) in an X-ray diffraction analysis spectrum obtained by X-ray diffraction analysis of the phosphorus sulfide composition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for manufacturing a sulfide-based inorganic solid electrolyte material, a method for manufacturing a phosphorus sulfide composition, a method for evaluating a phosphorus sulfide composition, and a phosphorus sulfide composition. Background Art

[0002] Generally, a lithium-ion battery is used as a power source for small portable devices such as mobile phones and laptop computers. In addition, recently, in addition to small portable devices, lithium-ion batteries have also begun to be used as power sources for electric vehicles, power storage, etc.

[0003] Currently, commercially available lithium-ion batteries use an electrolyte containing a flammable organic solvent. On the other hand, a lithium-ion battery (hereinafter, also referred to as a all-solid-state lithium-ion battery) in which the electrolyte is replaced with a solid electrolyte and the battery is made all-solid-state does not use a flammable organic solvent in the battery. Therefore, it can be considered that the simplification of the safety device is achieved and the manufacturing cost and productivity are excellent.

[0004] As such a solid electrolyte material used in such a solid electrolyte, for example, a sulfide-based inorganic solid electrolyte material is known.

[0005] In Patent Document 1 (Japanese Patent Application Laid-Open No. 2016-27545), a sulfide-based solid electrolyte material is described, which is characterized in that it has a peak at a position of 2θ = 29.86° ± 1.00° in X-ray diffraction measurement using CuKα rays and has a composition of Li 2y+3 PS4 (0.1 ≤ y ≤ 0.175).

[0006] Prior Art Documents

[0007] Patent Documents

[0008] Patent Document 1: Japanese Patent Application Laid-Open No. 2016-27545. Summary of the Invention

[0009] Problems to be Solved by the Invention

[0010] According to the research by the present inventors, it has been clarified that if the type of phosphorus sulfide (for example, manufacturing company, manufacturing batch, manufacturing method), which is one of the raw materials of the sulfide-based inorganic solid electrolyte material, is changed, the lithium ion conductivity of the obtained sulfide-based inorganic solid electrolyte material sometimes becomes low.

[0011] The present invention has been completed in view of the above circumstances, and provides a method for manufacturing a sulfide-based inorganic solid electrolyte material, a method for manufacturing a phosphorus sulfide composition, a method for evaluating a phosphorus sulfide composition, and a phosphorus sulfide composition capable of stably obtaining a sulfide-based inorganic solid electrolyte material with improved lithium ion conductivity.

[0012] Means for Solving the Problem

[0013] The inventors of the present invention have conducted intensive research to achieve the above problems. As a result, it has been found that by using a phosphorus sulfide composition having a specific X-ray distribution as a raw material for a sulfide-based inorganic solid electrolyte material, a sulfide-based inorganic solid electrolyte material with improved lithium ion conductivity can be stably obtained, and the present invention has been completed.

[0014] The inventors of the present invention have conducted intensive research to provide a sulfide-based inorganic solid electrolyte material with improved lithium ion conductivity. As a result, it has been found that if a phosphorus sulfide composition in which the content and crystallinity of P2S5 are respectively in specific ranges is used as a raw material when manufacturing a sulfide-based inorganic solid electrolyte material, the lithium ion conductivity of the obtained sulfide-based inorganic solid electrolyte material can be improved, and thus the present invention has been completed.

[0015] According to the present invention, there are provided a method for manufacturing a sulfide-based inorganic solid electrolyte material as shown below, a sulfide-based inorganic solid electrolyte material, a method for manufacturing a phosphorus sulfide composition, a method for evaluating a phosphorus sulfide composition, a phosphorus sulfide composition, a raw material composition for a sulfide-based inorganic solid electrolyte material, a sulfide-based inorganic solid electrolyte, a sulfide-based inorganic solid electrolyte film, and a lithium ion battery.

[0016] [1] A method for manufacturing a sulfide-based inorganic solid electrolyte material, wherein the method for manufacturing the sulfide-based inorganic solid electrolyte material includes a step of obtaining a glassy sulfide-based inorganic solid electrolyte material by subjecting a raw material composition for a sulfide-based inorganic solid electrolyte material containing lithium sulfide and a phosphorus sulfide composition to mechanical treatment to cause a chemical reaction among the components while vitrifying, and the phosphorus sulfide composition has three or more peaks in the range of 2θ = 22.5° or more and 24.5° or less in the X-ray diffraction analysis spectrum obtained by the method described in the following <X-ray Diffraction Analysis>.

[0017] <X-ray Diffraction Analysis>

[0018] Using an X-ray diffractometer, under the conditions of a voltage of 40 kV, a current of 40 mA, a divergence slit of 1°, a longitudinal limit of the divergence slit of 10 mm, a scattering slit of 1°, a receiving slit of 0.3 mm, a measurement start angle of 3°, a measurement end angle of 90°, and a scanning speed of 0.2° / minute, using CuKα rays as the radiation source, the phosphorus sulfide composition is placed in an airtight sample holder filled with argon to obtain the X-ray diffraction analysis spectrum of the phosphorus sulfide composition.

[0019] [2] The method for manufacturing a sulfide-based inorganic solid electrolyte material according to the foregoing [1], wherein the phosphorus sulfide composition contains P2S5.

[0020] [3] The manufacturing method of the sulfide-based inorganic solid electrolyte material as described in [2] above, wherein the content of P2S5 in the phosphorus sulfide composition is 20% by mass or more.

[0021] [4] The manufacturing method of the sulfide-based inorganic solid electrolyte material as described in any one of [1] to [3] above, wherein the phosphorus sulfide composition is in powder form.

[0022] [5] The manufacturing method of the sulfide-based inorganic solid electrolyte material as described in any one of [1] to [4] above, wherein the mechanical treatment includes mechanochemical treatment.

[0023] [6] The manufacturing method of the sulfide-based inorganic solid electrolyte material as described in any one of [1] to [5] above, wherein the manufacturing method of the sulfide-based inorganic solid electrolyte material further includes a step of heat-treating the glassy sulfide-based inorganic solid electrolyte material in the range of 180 °C or higher and 500 °C or lower.

[0024] [7] The manufacturing method of the sulfide-based inorganic solid electrolyte material as described in any one of [1] to [6] above, wherein the lithium ion conductivity of the sulfide-based inorganic solid electrolyte material measured by the method described in <Measurement of Lithium Ion Conductivity> below is 1.0×10 -3 S / cm or more.

[0025] <Measurement of Lithium Ion Conductivity>

[0026] First, 110 mg of the sulfide-based inorganic solid electrolyte material is pressurized under the conditions of 270 MPa and 10 minutes to obtain a disk-shaped specimen with a diameter of 9.5 mm and a thickness of 1 mm. Then, using an electrochemical measurement device, under the conditions of applying a voltage of 10 mV, a measurement frequency range of 0.1 Hz to 3 MHz, and a measurement temperature of 27 °C, using a Li foil as the electrode, the lithium ion conductivity of the obtained disk-shaped specimen is measured by the alternating current impedance method.

[0027] [8] A sulfide-based inorganic solid electrolyte material, wherein the sulfide-based inorganic solid electrolyte material is a sulfide-based inorganic solid electrolyte material obtained by the manufacturing method of the sulfide-based inorganic solid electrolyte material as described in any one of [1] to [7] above.

[0028] [9]A method for manufacturing a phosphorus sulfide composition, wherein the method for manufacturing the phosphorus sulfide composition includes a step of sorting a phosphorus sulfide composition having three or more peaks in the range of 2θ = 22.5° or more and 24.5° or less in the X-ray diffraction analysis spectrum obtained by the method described in the following <X-ray diffraction analysis>.

[0029] <X-ray diffraction analysis>

[0030] Using an X-ray diffractometer, under the conditions of a voltage of 40 kV, a current of 40 mA, a divergence slit of 1°, a longitudinal limit of the divergence slit of 10 mm, a scattering slit of 1°, a receiving slit of 0.3 mm, a measurement start angle of 3°, a measurement end angle of 90°, and a scanning speed of 0.2° / minute, using CuKα rays as the radiation source, the phosphorus sulfide composition is placed in an airtight sample holder filled with argon to obtain the X-ray diffraction analysis spectrum of the phosphorus sulfide composition.

[0031]

[10] The method for manufacturing a phosphorus sulfide composition according to the foregoing [9], wherein the phosphorus sulfide composition contains P2S5.

[0032]

[11] The method for manufacturing a phosphorus sulfide composition according to the foregoing

[10] , wherein the content of P2S5 in the phosphorus sulfide composition is 20% by mass or more.

[0033]

[12] The method for manufacturing a phosphorus sulfide composition according to any one of the foregoing [9] to

[11] , wherein the phosphorus sulfide composition is in powder form.

[0034]

[13] A method for manufacturing a sulfide-based inorganic solid electrolyte material, wherein the method for manufacturing the sulfide-based inorganic solid electrolyte material includes: a step of obtaining a phosphorus sulfide composition by using the method for manufacturing a phosphorus sulfide composition according to any one of the foregoing [9] to

[12] ; and a step of subjecting a raw material composition of the sulfide-based inorganic solid electrolyte material containing lithium sulfide and the phosphorus sulfide composition to mechanical treatment to cause chemical reactions among the components while vitrifying to obtain a glassy sulfide-based inorganic solid electrolyte material.

[0035]

[14] The method for manufacturing a sulfide-based inorganic solid electrolyte material according to the foregoing

[13] , wherein the mechanical treatment includes mechanochemical treatment.

[0036]

[15] The method for manufacturing a sulfide-based inorganic solid electrolyte material according to the foregoing

[13] or

[14] , wherein the method for manufacturing the sulfide-based inorganic solid electrolyte material further includes a step of heat-treating the glassy sulfide-based inorganic solid electrolyte material in the range of 180°C or more and 500°C or less.

[0037]

[16] The manufacturing method of the sulfide-based inorganic solid electrolyte material according to any one of the foregoing

[13] to

[15] , wherein the lithium ion conductivity of the sulfide-based inorganic solid electrolyte material measured by the method described in the following <Measurement of Lithium Ion Conductivity> is 1.0×10 -3 S / cm or more.

[0038] <Measurement of Lithium Ion Conductivity>

[0039] First, pressurize 110 mg of the sulfide-based inorganic solid electrolyte material under the conditions of 270 MPa and 10 minutes to obtain a disc-shaped specimen with a diameter of 9.5 mm and a thickness of 1 mm. Then, using an electrochemical measurement device, under the conditions of applying a voltage of 10 mV, a measurement frequency range of 0.1 Hz to 3 MHz, and a measurement temperature of 27°C, using a Li foil as the electrode, measure the lithium ion conductivity of the obtained disc-shaped specimen by the AC impedance method.

[0040]

[17] A sulfide-based inorganic solid electrolyte material, wherein the sulfide-based inorganic solid electrolyte material is a sulfide-based inorganic solid electrolyte material obtained by the manufacturing method of the sulfide-based inorganic solid electrolyte material according to any one of the foregoing

[13] to

[16] .

[0041]

[18] An evaluation method of a phosphorus sulfide composition, wherein the evaluation method of the phosphorus sulfide composition includes a step of determining that a phosphorus sulfide composition having three or more peaks in the range of 2θ = 22.5° or more and 24.5° or less in the X-ray diffraction analysis spectrum obtained by the method described in the following <X-ray Diffraction Analysis> is qualified.

[0042] <X-ray Diffraction Analysis>

[0043] Using an X-ray diffractometer, under the conditions of a voltage of 40 kV, a current of 40 mA, a divergence slit of 1°, a longitudinal limit of the divergence slit of 10 mm, a scatter slit of 1°, a receiving slit of 0.3 mm, a measurement start angle of 3°, a measurement end angle of 90°, and a scanning speed of 0.2° / minute, using CuKα rays as the radiation source, setting the phosphorus sulfide composition in an airtight specimen holder filled with argon, and obtaining the X-ray diffraction analysis spectrum of the phosphorus sulfide composition.

[0044]

[19] The evaluation method of the phosphorus sulfide composition according to the foregoing

[18] , wherein the phosphorus sulfide composition contains P2S5.

[0045]

[20] The evaluation method of the phosphorus sulfide composition according to the foregoing

[19] , wherein the content of P2S5 in the phosphorus sulfide composition is 20% by mass or more.

[0046]

[21] The evaluation method of the phosphorus sulfide composition according to any one of the foregoing

[18] to

[20] , wherein the phosphorus sulfide composition is in powder form.

[0047]

[22] A phosphorus sulfide composition, which is a phosphorus sulfide composition for a sulfide-based inorganic solid electrolyte material containing at least P2S5 and P4S9. When the total content of P2S5, P4S9, P4S7, and P4S3 in the phosphorus sulfide composition is set to 100% by mass, according to the solid 31 The content of P2S5 calculated by P-NMR spectroscopy is 30% by mass or more and 60% by mass or less, and the crystallinity calculated from the spectrum obtained by X-ray diffraction using CuKα rays as the radiation source is 40% or more and 70% or less.

[0048]

[23] The phosphorus sulfide composition according to the foregoing

[22] , wherein the content of P4S9 calculated by solid 31 P-NMR spectroscopy is 40% by mass or more and 70% by mass or less.

[0049]

[24] The phosphorus sulfide composition according to the foregoing

[22] or

[23] , wherein the total content of P2S5 and P4S9 is 90% by mass or more.

[0050]

[25] The phosphorus sulfide composition according to any one of the foregoing

[22] to

[24] , wherein in the differential scanning calorimetry (DSC) curve of the phosphorus sulfide composition obtained by measurement with a differential scanning calorimeter, an endothermic peak is observed in the temperature range of 280 °C or higher and 300 °C or lower, and the heat of fusion of the endothermic peak is 60 J / g or more and 90 J / g or less.

[0051]

[26] The phosphorus sulfide composition according to any one of the foregoing

[22] to

[25] , wherein the phosphorus sulfide composition is in powder form.

[0052]

[27] A raw material composition for a sulfide-based inorganic solid electrolyte material, wherein the raw material composition for the sulfide-based inorganic solid electrolyte material contains the phosphorus sulfide composition according to any one of the foregoing

[22] to

[26] and lithium sulfide.

[0053]

[28] A method for manufacturing a sulfide-based inorganic solid electrolyte material, wherein the method for manufacturing the sulfide-based inorganic solid electrolyte material includes a step of mechanically treating the raw material composition for the sulfide-based inorganic solid electrolyte material according to the foregoing

[27] .

[0054]

[29] A sulfide-based inorganic solid electrolyte material, wherein the sulfide-based inorganic solid electrolyte material contains a mechanically treated product of the raw material composition of the sulfide-based inorganic solid electrolyte material described in the foregoing

[27] .

[0055]

[30] A sulfide-based inorganic solid electrolyte, wherein the sulfide-based inorganic solid electrolyte contains the sulfide-based inorganic solid electrolyte material described in any one of the foregoing [8],

[17] , and

[29] .

[0056]

[31] A sulfide-based inorganic solid electrolyte membrane, wherein the sulfide-based inorganic solid electrolyte membrane contains, as a main component, the sulfide-based inorganic solid electrolyte described in the foregoing

[30] .

[0057]

[32] A lithium-ion battery, which is a lithium-ion battery including a positive electrode having a positive electrode active material layer, an electrolyte layer, and a negative electrode having a negative electrode active material layer, wherein at least one of the positive electrode active material layer, the electrolyte layer, and the negative electrode active material layer contains the sulfide-based inorganic solid electrolyte material described in any one of the foregoing [8],

[17] , and

[29] .

[0058] Effects of the Invention

[0059] According to the present invention, it is possible to provide a method for manufacturing a sulfide-based inorganic solid electrolyte material capable of stably obtaining a sulfide-based inorganic solid electrolyte material with improved lithium ion conductivity, a method for manufacturing a phosphorus sulfide composition, a method for evaluating a phosphorus sulfide composition, and a phosphorus sulfide composition. Description of the Drawings

[0060] Figure 1 It is a cross-sectional view showing an example of the structure of the lithium-ion battery of the present embodiment.

[0061] Figure 2 It is a graph showing the X-ray diffraction analysis spectra of the phosphorus sulfide compositions used in the examples and comparative examples.

[0062] Figure 3 It is a graph showing an enlarged view of the range of 2θ = 20 to 30° of the X-ray diffraction analysis spectra of the phosphorus sulfide compositions used in the examples and comparative examples.

[0063] Figure 4 It is a graph showing the X-ray diffraction spectrum for explaining the method (peak separation method) for calculating the crystallinity of the phosphorus sulfide composition of the third embodiment.

[0064] Figure 5 It is a graph for explaining the baseline used when calculating the heat of fusion of the endothermic peak. Detailed Description of the Invention

[0065] Hereinafter, embodiments of the present invention will be described with reference to the accompanying drawings. It should be noted that in all the drawings, the same reference numerals are assigned to the same constituent elements, and appropriate descriptions are omitted. In addition, the drawings are schematic diagrams and do not match the actual dimensional ratios. Unless otherwise specified, the numerical range of "A to B" means A or more and B or less. It should be noted that unless otherwise specified, "this embodiment" refers to the embodiment including all the first to third embodiments.

[0066] <First Embodiment>

[0067] A method for manufacturing a sulfide-based inorganic solid electrolyte material and a sulfide-based inorganic solid electrolyte material according to the first embodiment will be described.

[0068] [Method for Manufacturing Sulfide-Based Inorganic Solid Electrolyte Material]

[0069] The method for manufacturing a sulfide-based inorganic solid electrolyte material according to the first embodiment includes a step of subjecting a raw material composition of a sulfide-based inorganic solid electrolyte material containing a lithium sulfide and a phosphorus sulfide composition to mechanical treatment to cause a chemical reaction among the components while vitrifying to obtain a glassy sulfide-based inorganic solid electrolyte material. And, for the phosphorus sulfide composition of the first embodiment, there are three or more peaks in the range of 2θ = 22.5° or more and 24.5° or less in the X-ray diffraction analysis spectrum obtained by the method described in the following <X-ray Diffraction Analysis>.

[0070] <X-ray Diffraction Analysis>

[0071] Using an X-ray diffractometer, under the conditions of a voltage of 40 kV, a current of 40 mA, a divergence slit of 1°, a longitudinal limit of the divergence slit of 10 mm, a scattering slit of 1°, a receiving slit of 0.3 mm, a measurement start angle of 3°, a measurement end angle of 90°, and a scanning speed of 0.2° / minute, using CuKα rays as the radiation source, the phosphorus sulfide composition is placed in an airtight sample holder filled with argon to obtain the X-ray diffraction analysis spectrum of the phosphorus sulfide composition.

[0072] According to the research of the present inventors, it has been clarified that if the type of phosphorus sulfide (for example, manufacturing company, manufacturing batch, manufacturing method), which is one of the raw materials of the sulfide-based inorganic solid electrolyte material, is changed, the lithium ion conductivity of the obtained sulfide-based inorganic solid electrolyte material sometimes becomes low.

[0073] Therefore, the present inventors have intensively studied to provide a method for manufacturing a sulfide-based inorganic solid electrolyte material with improved lithium ion conductivity stably. As a result, it has been found that by using a phosphorus sulfide composition having three or more peaks observed in the range of 2θ = 22.5° or more and 24.5° or less in the X-ray diffraction analysis spectrum as a raw material for the sulfide-based inorganic solid electrolyte material, a decrease in the lithium ion conductivity of the obtained sulfide-based inorganic solid electrolyte material can be suppressed, and thus the present invention has been completed.

[0074] That is, according to the method for manufacturing a sulfide-based inorganic solid electrolyte material of the first embodiment, by using a phosphorus sulfide composition having three or more peaks observed in the range of 2θ = 22.5° or more and 24.5° or less in the X-ray diffraction analysis spectrum as a raw material for the sulfide-based inorganic solid electrolyte material, a sulfide-based inorganic solid electrolyte material with improved lithium ion conductivity can be obtained stably.

[0075] The method for manufacturing a sulfide-based inorganic solid electrolyte material of the first embodiment includes the following step (A), and may further include step (B) and step (C). Step (C) may be carried out between step (A) and step (B), or may be carried out after step (B).

[0076] Step (A): A step of obtaining a glassy sulfide-based inorganic solid electrolyte material by subjecting a raw material composition of a sulfide-based inorganic solid electrolyte material containing lithium sulfide and a phosphorus sulfide composition to mechanical treatment to cause a chemical reaction between the components and simultaneously vitrifying.

[0077] Step (B): A step of heating the obtained glassy sulfide-based inorganic solid electrolyte material to crystallize at least a part thereof to obtain a glass-ceramic state sulfide-based inorganic solid electrolyte material.

[0078] Step (C): A step of pulverizing, classifying or granulating the obtained glass or glass-ceramic state sulfide-based inorganic solid electrolyte material.

[0079] (Step (A))

[0080] First, prepare a raw material composition of a sulfide-based inorganic solid electrolyte material. The raw material composition of the sulfide-based inorganic solid electrolyte material contains lithium sulfide and a phosphorus sulfide composition, and may further contain lithium nitride as needed.

[0081] Here, adjust the mixing ratio of each raw material in the raw material composition so that the obtained sulfide-based inorganic solid electrolyte material has a desired composition ratio.

[0082] A method for mixing the respective raw materials may be any mixing method capable of uniformly mixing the respective raw materials, and there is no particular limitation. For example, a ball mill, a bead mill, a vibration mill, a percussion crushing device, a mixer (such as a pugmixer, a ribbon mixer, a drum mixer, a rotary drum mixer, a V-type mixer, etc.), a kneader, a twin-screw kneader, a jet mill, a crusher, a rotary knife type crusher, etc. can be used for mixing.

[0083] Mixing conditions such as the stirring speed, treatment time, temperature, reaction pressure, and gravitational acceleration applied to the mixture when mixing the respective raw materials can be appropriately determined according to the treatment amount of the mixture.

[0084] In step (A), by mechanically treating the raw material composition of the sulfide-based inorganic solid electrolyte material containing lithium sulfide and a phosphorus sulfide composition, while causing a chemical reaction among the respective components, vitrification is carried out, thereby obtaining a glassy sulfide-based inorganic solid electrolyte material.

[0085] Here, mechanical treatment refers to a treatment capable of causing a chemical reaction among two or more inorganic compounds by mechanical collision while carrying out vitrification, for example, mechanochemical treatment, etc. Here, mechanochemical treatment refers to a method of carrying out vitrification while applying mechanical energy such as shear force and collision force to the target composition.

[0086] In addition, in step (A), from the viewpoint of easily achieving an environment for removing moisture and oxygen at a high level, the mechanochemical treatment is preferably a dry mechanochemical treatment.

[0087] If mechanochemical treatment is used, it is possible to mix while pulverizing the respective raw materials into fine particles, and thus, the contact area of the respective raw materials can be increased. Thereby, the reaction of the respective raw materials can be promoted, and thus, the sulfide-based inorganic solid electrolyte material of the first embodiment can be obtained more efficiently.

[0088] Here, mechanochemical treatment refers to a method of carrying out vitrification while applying mechanical energy such as shear force, collision force, and centrifugal force to the mixing object. As a device for carrying out vitrification by mechanochemical treatment (hereinafter, referred to as a vitrification device), a ball mill, a bead mill, a vibration mill, a turbo mill, a mechanical fusion machine, a disk mill, a roller mill, etc., which are crushing / dispersing machines; a rotary / striking crushing device composed of a mechanism combining rotation (shearing stress) and striking (compressive stress) represented by a rock drill, a vibration drill, an impact driver, etc.; a high-pressure type grinding roll; a vertical roller mill such as a roller type vertical mill and a ball type vertical mill, etc. can be cited.

[0089] Among them, from the viewpoint of being able to efficiently generate very high impact energy, a ball mill and a bead mill are preferred, and a ball mill is more preferred.

[0090] In addition, from the viewpoint of excellent continuous productivity, a roll mill is preferred; a rotary / striking crushing device composed of a mechanism combining rotation (shearing stress) and striking (compressive stress) represented by a rock drill, a rotary drill, an impact drill, etc.; a high-pressure type grinding roll; a vertical mill such as a roller vertical mill and a ball vertical mill.

[0091] When mechanically treating the raw material composition of the sulfide-based inorganic solid electrolyte material, the mixing conditions such as the rotation speed, treatment time, temperature, reaction pressure, and gravitational acceleration applied to the raw material composition can be appropriately determined according to the type and treatment amount of the raw material composition. Generally, the faster the rotation speed, the faster the glass formation rate, and the longer the treatment time, the higher the conversion rate into glass.

[0092] Generally, when using CuKα rays as the radiation source for X-ray diffraction analysis, after the diffraction peaks from the raw materials disappear or decrease, it can be judged that the raw material composition of the sulfide-based inorganic solid electrolyte material has been vitrified, and the desired sulfide-based inorganic solid electrolyte material can be obtained.

[0093] It is preferred that the mechanical treatment in step (A) is carried out in an inert gas atmosphere. Thereby, the deterioration (for example, oxidation) of the sulfide-based inorganic solid electrolyte material can be prevented.

[0094] As the inert gas, for example, argon, helium, nitrogen, etc. can be cited. In order to prevent impurities from mixing into the product, the higher the purity of these inert gases, the more preferred. In addition, in order to avoid contact with moisture, the dew point is preferably -70°C or lower, and more preferably -80°C or lower.

[0095] Here, in step (A), it is preferred to carry out the vitrification treatment until the lithium ion conductivity of the sulfide-based inorganic solid electrolyte material based on the alternating current impedance method under the measurement conditions of 27.0°C, an applied voltage of 10 mV, and a measurement frequency range of 0.1 Hz to 3 MHz is preferably 1.0×10 -4 S·cm -1 or more, more preferably 2.0×10 -4 S·cm -1 or more, further preferably 3.0×10 -4 S·cm -1 or more, further preferably 4.0×10 -4 S·cm -1 or more. Thereby, a sulfide-based inorganic solid electrolyte material with further excellent lithium ion conductivity can be obtained.

[0096] <Phosphorus sulfide composition>

[0097] For the phosphorus sulfide composition of the first embodiment, in the X-ray diffraction analysis spectrum obtained by the method described in the aforementioned <X-ray diffraction analysis>, there are three or more peaks in the range of 2θ = 22.5° or more and 24.5° or less, and preferably three peaks.

[0098] The phosphorus sulfide composition of the first embodiment contains, for example, one or more selected from the group consisting of P2S5 (also denoted as P4S 10 ), P4S9, P4S7, P4S3, and P4S5, preferably contains one or two selected from the group consisting of P2S5 and P4S9, and more preferably contains P2S5 and P4S9.

[0099] From the viewpoint of further improving the lithium ion conductivity of the sulfide-based inorganic solid electrolyte material of the first embodiment, when the total amount of the phosphorus sulfide composition of the first embodiment is set to 100% by mass, the content of P2S5 in the phosphorus sulfide composition of the first embodiment is preferably 20% by mass or more, more preferably 30% by mass or more, further preferably 35% by mass or more, further preferably 40% by mass or more, and preferably 80% by mass or less, more preferably 70% by mass or less, further preferably 60% by mass or less, further preferably 55% by mass or less, and further preferably 50% by mass or less.

[0100] Here, the content of P2S5 in the phosphorus sulfide composition of the first embodiment can be calculated from the solid 31 P-NMR spectrum.

[0101] From the viewpoint of further improving the lithium ion conductivity of the sulfide-based inorganic solid electrolyte material of the first embodiment, when the total amount of the phosphorus sulfide composition of the first embodiment is set to 100% by mass, the content of P4S9 in the phosphorus sulfide composition of the first embodiment is preferably 20% by mass or more, more preferably 30% by mass or more, further preferably 40% by mass or more, further preferably 45% by mass or more, further preferably 50% by mass or more, and preferably 80% by mass or less, more preferably 70% by mass or less, further preferably 65% by mass or less, and further preferably 60% by mass or less.

[0102] Here, the content of P4S9 in the phosphorus sulfide composition of the first embodiment can be calculated from the solid 31 P-NMR spectrum.

[0103] Preferably, the phosphorus sulfide composition of the first embodiment contains P2S5 and P4S9. From the viewpoint of further improving the lithium ion conductivity of the sulfide-based inorganic solid electrolyte material of the first embodiment, when the total amount of the phosphorus sulfide composition of the first embodiment is set to 100% by mass, the total content of P2S5 and P4S9 in the phosphorus sulfide composition of the first embodiment is preferably 90% by mass or more, more preferably 95% by mass or more, further preferably 97% by mass or more, further preferably 98% by mass or more, and further preferably 99% by mass or more. The upper limit of the total content of P2S5 and P4S9 in the phosphorus sulfide composition of the first embodiment is not particularly limited, and is, for example, 100% by mass or less.

[0104] solid 31 The 31P-NMR spectrum can be measured, for example, by the following method.

[0105] First, in a glove box purged with N2 gas, a test sample is filled in a measuring sample tube with a diameter of 3.2 mm, and it is rotated in a state inclined at a magic angle (54.7 degrees) with respect to the external magnetic field (Magic Angle Spining: MAS, magic angle rotation), and the measurement is performed under the following conditions.

[0106] Apparatus: JNM-ECA-600 manufactured by JEOL Resonance Inc.

[0107] Observation frequency: 242.95 MHz.

[0108] Pulse width: 90° pulse.

[0109] Pulse delay time: 2800 seconds.

[0110] Number of integration operations: 64 times.

[0111] Measurement mode: single pulse method.

[0112] Magic angle rotation (MAS) speed: 12 kHz.

[0113] Standard substance: (NH4)2HPO4·1.33 ppm.

[0114] For the peaks detected in the 31 31P-NMR spectrum of the test sample, refer to Reference 1 "Hellmut Eckert, Cheryl S. Liang and Galen D. Stucky: 31P magic angle spinning NMR of crystalline phosphorous sulfides. Correlation of 31 P chemical shielding tensors with local environments, J. Phys. Chem, 1989, 93, 452 - 457”. Based on the following peak assignments, waveform separation using Gaussian functions was performed to calculate the integral values of each peak. The integral values of the peaks from each component are proportional to the molar number of phosphorus contained. Therefore, the content ratio can be calculated based on the obtained integral values and the molecular weights of the respective components.

[0115] The chemical shift of P2S5 is 40 - 52 ppm, the chemical shift of P4S9 is 52 - 70 ppm, the chemical shifts of P4S7 are 80 - 90 ppm, 90 - 100 ppm, 110 - 115 ppm, and the chemical shifts of P4S3 are 80 - 90 ppm, 90 - 100 ppm.

[0116] As the properties of the phosphorus sulfide composition of the first embodiment, for example, a powdery form can be cited. Since the production of the sulfide - based inorganic solid electrolyte material of the first embodiment is usually carried out dry, if the properties of the phosphorus sulfide composition of the first embodiment are in a powdery form, it is easier to produce the sulfide - based inorganic solid electrolyte material.

[0117] <Lithium sulfide>

[0118] Lithium sulfide used as a raw material is not particularly limited, and commercially available lithium sulfide can be used. For example, lithium sulfide obtained by the reaction of lithium hydroxide and hydrogen sulfide can also be used. From the viewpoints of obtaining a high - purity sulfide - based inorganic solid electrolyte material and suppressing side reactions, lithium sulfide with few impurities is preferably used.

[0119] Here, in the first embodiment, lithium sulfide also includes polysulfide.

[0120] <Lithium nitride>

[0121] Lithium nitride can also be used as a raw material. Here, since nitrogen in lithium nitride is discharged out of the system in the form of N2, by using lithium nitride as a raw material, for the sulfide - based inorganic solid electrolyte material containing Li, P, and S as constituent elements, only the Li composition can be increased.

[0122] Lithium nitride of the first embodiment is not particularly limited, and commercially available lithium nitride (for example, Li3N, etc.) can be used. For example, lithium nitride obtained by the reaction of metallic lithium (for example, Li foil) and nitrogen can be used.

[0123] In the method for manufacturing a sulfide-based inorganic solid electrolyte material according to the first embodiment, from the viewpoints of obtaining a high-purity solid electrolyte material and suppressing side reactions, lithium nitride with few impurities is preferably used.

[0124] Here, the ratio of each raw material in the raw material composition can be adjusted so that the sulfide-based inorganic solid electrolyte material has a desired composition ratio.

[0125] (Step (B))

[0126] In step (B), the obtained glassy sulfide-based inorganic solid electrolyte material is heated to crystallize at least a part thereof, thereby obtaining a glass-ceramic-state sulfide-based inorganic solid electrolyte material. Thereby, a sulfide-based inorganic solid electrolyte material having further excellent lithium ion conductivity can be obtained.

[0127] That is, from the viewpoint of excellent lithium ion conductivity, the sulfide-based inorganic solid electrolyte material of the first embodiment is preferably in a glass-ceramic state (crystallized glass state). Here, glass ceramic refers to a substance in which at least a part of an inorganic compound is crystallized, and is also called crystallized glass.

[0128] The heat treatment temperature in step (B) is not particularly limited. From the viewpoint of further improving the lithium ion conductivity of the sulfide-based inorganic solid electrolyte material of the first embodiment, it is preferably 180 °C or higher, more preferably 200 °C or higher, further preferably 220 °C or higher, and preferably 500 °C or lower, more preferably 450 °C or lower, further preferably 400 °C or lower, and further preferably 350 °C or lower.

[0129] The heat treatment time in step (B) is not particularly limited as long as it is a time that can obtain the desired glass-ceramic-state sulfide-based inorganic solid electrolyte material. From the viewpoint of further improving the lithium ion conductivity of the sulfide-based inorganic solid electrolyte material of the first embodiment, it is preferably 0.5 hour or longer, more preferably 1 hour or longer, and preferably 24 hours or shorter, more preferably 3 hours or shorter.

[0130] In addition, the method of heat treatment in step (B) is not particularly limited. For example, a method using a heating furnace or a firing furnace can be cited. It should be noted that conditions such as the temperature and time during such heating can be appropriately adjusted to optimize the characteristics of the sulfide-based inorganic solid electrolyte material of the first embodiment.

[0131] In addition, from the viewpoint of preventing deterioration (for example, oxidation) of the sulfide-based inorganic solid electrolyte material, it is preferable that the heat treatment in step (B) is performed in an inert gas atmosphere.

[0132] As an inert gas when the sulfide-based inorganic solid electrolyte material is in a heated glass state, for example, argon, helium, nitrogen, etc. can be cited. In order to avoid impurities from mixing into the product, the higher the purity of these inert gases, the more preferable. In addition, in order to avoid contact with moisture, the dew point is preferably -30°C or lower, more preferably -70°C or lower, and particularly preferably -80°C or lower. As a method for introducing the inert gas into the mixing system, any method that fills the mixing system with an inert gas environment can be used, and there is no particular limitation. Examples include the method of purging the inert gas and the method of continuously introducing a specified amount of the inert gas.

[0133] (Process (C))

[0134] In the manufacturing method of the sulfide-based inorganic solid electrolyte material of the first embodiment, as needed, a process (C) of pulverizing, classifying, or granulating the obtained glass or glass-ceramic state sulfide-based inorganic solid electrolyte material can also be performed. For example, by pulverization for micronization, and then adjusting the particle size through classification operations and granulation operations, a sulfide-based inorganic solid electrolyte material with a desired particle size can be obtained. As the above-mentioned pulverization method, there is no particular limitation, and known pulverization methods such as mixers, jet mills, mortars, rotary mills, and coffee grinders can be used. In addition, as the above-mentioned classification method, there is no particular limitation, and known methods such as sieves can be used.

[0135] From the viewpoint of being able to prevent contact with moisture in the air, it is preferable that these pulverization or classification are carried out in an inert gas environment or a vacuum environment.

[0136] [Sulfide-based inorganic solid electrolyte material]

[0137] The sulfide-based inorganic solid electrolyte material of the first embodiment can be obtained by the manufacturing method of the sulfide-based inorganic solid electrolyte material of the first embodiment.

[0138] The sulfide-based inorganic solid electrolyte material of the first embodiment can be used for any application that requires lithium ion conductivity. Preferably, it can be used for lithium ion batteries, and more preferably, it can be used for all-solid-state lithium ion batteries.

[0139] From the viewpoint of further improving the input-output characteristics of the lithium ion battery, the lithium ion conductivity of the sulfide-based inorganic solid electrolyte material of the first embodiment measured by the method described in the following <Measurement of lithium ion conductivity> is preferably 1.0×10 -3 S / cm or more, more preferably 1.1×10 -3 S / cm or more, further preferably 1.2×10 -3 S / cm or more, and further preferably 1.3×10-3 above 1 S / cm, more preferably 1.4×10 -3 S / cm or more.

[0140] In addition, the lithium ion conductivity of the sulfide-based inorganic solid electrolyte material of the first embodiment is not particularly limited. For example, it is 1.0×10 -2 S / cm or less, and can be 5.0×10 -3 S / cm or less, and can be 3.0×10 -3 S / cm or less, and can also be 2.0×10 -3 S / cm or less.

[0141] <Measurement of lithium ion conductivity>

[0142] First, 110 mg of the sulfide-based inorganic solid electrolyte material is pressurized under the conditions of 270 MPa and 10 minutes to obtain a disk-shaped sample with a diameter of 9.5 mm and a thickness of 1 mm.

[0143] Then, using an electrochemical measurement device, under the conditions of applying a voltage of 10 mV, a measurement frequency range of 0.1 Hz to 3 MHz, and a measurement temperature of 27°C, using a Li foil as the electrode, the lithium ion conductivity of the obtained disk-shaped sample is measured by the AC impedance method.

[0144] It should be noted that the measurement of lithium ion conductivity can be performed using an electrochemical measurement device such as a potentiostat / galvanostat SP-300 manufactured by Bio-Logic Science Instruments.

[0145] Preferably, the sulfide-based inorganic solid electrolyte material of the first embodiment has good electrochemical stability. Here, electrochemical stability refers to the property of being difficult to be oxidized or reduced in a wide voltage range, for example. More specifically, in the sulfide-based inorganic solid electrolyte material of the first embodiment, the maximum value of the oxidation decomposition current of the sulfide-based inorganic solid electrolyte material measured under the conditions of a temperature of 25°C, a scanning voltage range of 0 to 5 V, and a voltage scanning speed of 5 mV / second is preferably 0.50 μA or less, more preferably 0.20 μA or less, further preferably 0.10 μA or less, further preferably 0.05 μA or less, and further preferably 0.03 μA or less.

[0146] If the maximum value of the oxidation decomposition current of the sulfide-based inorganic solid electrolyte material is below the above upper limit value, the oxidation decomposition of the sulfide-based inorganic solid electrolyte material in the lithium ion battery can be suppressed, so it is preferred.

[0147] The lower limit of the maximum value of the oxidation decomposition current of the sulfide-based inorganic solid electrolyte material is not particularly limited, and is, for example, 0.0001 μA or more.

[0148] The sulfide-based inorganic solid electrolyte material of the first embodiment can be used for any application that requires lithium ion conductivity. Among them, it is preferred that the sulfide-based inorganic solid electrolyte material of the first embodiment be used in a lithium ion battery. More specifically, it is preferably used in a positive electrode active material layer, a negative electrode active material layer, an electrolyte layer, etc. in a lithium ion battery. Further, the sulfide-based inorganic solid electrolyte material of the first embodiment is suitable for constituting a positive electrode active material layer, a negative electrode active material layer, a solid electrolyte layer, etc. of an all-solid-state lithium ion battery, and is more suitable for constituting a solid electrolyte layer of an all-solid-state lithium ion battery.

[0149] As an example of an all-solid-state lithium ion battery using the sulfide-based inorganic solid electrolyte material of the first embodiment, a battery in which a positive electrode, a solid electrolyte layer, and a negative electrode are laminated in this order can be cited.

[0150] From the viewpoints of further improving electrochemical stability, stability in moisture and air, and operability, etc., it is preferred that the sulfide-based inorganic solid electrolyte material of the first embodiment contains Li, P, and S as constituent elements.

[0151] In addition, for the sulfide-based inorganic solid electrolyte material of the first embodiment, from the viewpoints of improving the performance balance of lithium ion conductivity and electrochemical stability and from the viewpoints of further improving the stability and operability in moisture or air, the molar ratio of Li to P, Li / P, in the sulfide-based inorganic solid electrolyte material of the first embodiment is preferably 1.0 or more and 5.0 or less, more preferably 2.0 or more and 4.0 or less, further preferably 2.5 or more and 3.8 or less, further preferably 2.7 or more and 3.6 or less, further preferably 2.8 or more and 3.5 or less, further preferably 2.9 or more and 3.4 or less, further preferably 3.0 or more and 3.3 or less, and the molar ratio of S to P, S / P, is preferably 2.0 or more and 6.0 or less, more preferably 3.0 or more and 5.0 or less, further preferably 3.5 or more and 4.5 or less, further preferably 3.8 or more and 4.2 or less, further preferably 3.9 or more and 4.1 or less, and further preferably 4.0.

[0152] From the viewpoints of improving the performance balance of lithium ion conductivity and electrochemical stability and from the viewpoints of further improving the stability and operability in moisture or air, it is preferred that the sulfide-based inorganic solid electrolyte material of the first embodiment contains from Li3PS4 and Li 10 P3S 12One or two selected from the group consisting of.

[0153] Here, the contents of Li, P, and S in the sulfide-based inorganic solid electrolyte material of the first embodiment can be determined, for example, by inductively coupled plasma (ICP) optical emission spectrometry and X-ray analysis.

[0154] As the shape of the sulfide-based inorganic solid electrolyte material of the first embodiment, for example, particulate form can be cited.

[0155] The particulate sulfide-based inorganic solid electrolyte material of the first embodiment is not particularly limited, and the average particle diameter d in the weight-based particle size distribution according to the laser diffraction scattering type particle size distribution measurement method 50 is preferably 1 μm or more and 100 μm or less, more preferably 3 μm or more and 80 μm or less, and still more preferably 5 μm or more and 60 μm or less.

[0156] By setting the average particle diameter d of the sulfide-based inorganic solid electrolyte material 50 within the above range, good operability can be maintained and the lithium ion conductivity can be further improved.

[0157] <Second Embodiment>

[0158] A method for manufacturing a phosphorus sulfide composition, a method for evaluating a phosphorus sulfide composition, and a sulfide-based inorganic solid electrolyte material of the second embodiment will be described.

[0159] [Method for Manufacturing and Evaluating Phosphorus Sulfide Composition]

[0160] The method for manufacturing a phosphorus sulfide composition of the second embodiment includes a step of sorting a phosphorus sulfide composition in which three or more peaks are present in the range of 2θ = 22.5° or more and 24.5° or less in the X-ray diffraction analysis spectrum obtained by the method described in the following <X-ray Diffraction Analysis>.

[0161] <X-ray Diffraction Analysis>

[0162] Using an X-ray diffractometer, under the conditions of a voltage of 40 kV, a current of 40 mA, a divergence slit of 1°, a longitudinal limit of the divergence slit of 10 mm, a scatter slit of 1°, a receiving slit of 0.3 mm, a measurement start angle of 3°, a measurement end angle of 90°, and a scan speed of 0.2° / minute, using CuKα rays as the radiation source, the phosphorus sulfide composition is placed in an airtight sample holder filled with argon, and the X-ray diffraction analysis spectrum of the phosphorus sulfide composition is obtained.

[0163] In addition, the evaluation method of the phosphorus sulfide composition of the second embodiment includes a step of determining as qualified a phosphorus sulfide composition in which three or more peaks are present in the range of 2θ = 22.5° or more and 24.5° or less in the X-ray diffraction analysis spectrum obtained by the method described in the above <X-ray Diffraction Analysis>.

[0164] According to the research of the present inventors, it has been clarified that if the type of phosphorus sulfide (for example, manufacturing company, manufacturing batch, manufacturing method), which is one of the raw materials of the sulfide-based inorganic solid electrolyte material, is changed, the lithium ion conductivity of the obtained sulfide-based inorganic solid electrolyte material sometimes becomes low.

[0165] Therefore, the present inventors have intensively studied to provide a manufacturing method for stably obtaining a sulfide-based inorganic solid electrolyte material with improved lithium ion conductivity. As a result, it has been found that by using a phosphorus sulfide composition in which three or more peaks are observed in the range of 2θ = 22.5° or more and 24.5° or less in the X-ray diffraction analysis spectrum as a raw material of the sulfide-based inorganic solid electrolyte material, it is possible to suppress the decrease in the lithium ion conductivity of the obtained sulfide-based inorganic solid electrolyte material, and thus the present invention has been completed.

[0166] That is, according to the second embodiment, by sorting and using a phosphorus sulfide composition in which three or more peaks are observed in the range of 2θ = 22.5° or more and 24.5° or less in the X-ray diffraction analysis spectrum as a raw material of the sulfide-based inorganic solid electrolyte material, it is possible to stably obtain a sulfide-based inorganic solid electrolyte material with improved lithium ion conductivity.

[0167] In the manufacturing method and evaluation method of the phosphorus sulfide composition of the second embodiment, a raw material composition of phosphorus sulfide is prepared. The raw material composition of phosphorus sulfide used as the raw material is not particularly limited, and commercially available phosphorus sulfide can be directly used, or a raw material composition of phosphorus sulfide obtained by a generally known manufacturing method of phosphorus sulfide can be used. It is preferable to use phosphorus sulfide for sulfide-based inorganic solid electrolyte materials.

[0168] Then, in the manufacturing method of the phosphorus sulfide composition of the second embodiment, a phosphorus sulfide composition in which three or more peaks are present in the range of 2θ = 22.5° or more and 24.5° or less in the X-ray diffraction analysis spectrum obtained by the method described in the above <X-ray Diffraction Analysis> is sorted from the prepared raw material composition of phosphorus sulfide.

[0169] In addition, in the evaluation method of the phosphorus sulfide composition of the second embodiment, among the prepared raw material compositions of phosphorus sulfide, a phosphorus sulfide composition in which there are three or more peaks in the range of 2θ = 22.5° or more and 24.5° or less in the X-ray diffraction analysis spectrum obtained by the method described in the <X-ray Diffraction Analysis> is determined to be qualified.

[0170] In the X-ray diffraction analysis spectrum obtained by the method described in the <X-ray Diffraction Analysis>, the phosphorus sulfide composition of the second embodiment has three or more peaks in the range of 2θ = 22.5° or more and 24.5° or less, and preferably has three peaks.

[0171] The preferred mode of the phosphorus sulfide composition of the second embodiment is the same as that of the phosphorus sulfide composition of the first embodiment.

[0172] [Method for manufacturing sulfide-based inorganic solid electrolyte material]

[0173] The method for manufacturing a sulfide-based inorganic solid electrolyte material according to the second embodiment includes: a step of obtaining a phosphorus sulfide composition using the method for manufacturing a phosphorus sulfide composition according to the second embodiment; and a step of subjecting a raw material composition of a sulfide-based inorganic solid electrolyte material containing lithium sulfide and the phosphorus sulfide composition to mechanical treatment to cause a chemical reaction among the components while vitrifying to obtain a glassy sulfide-based inorganic solid electrolyte material.

[0174] That is, the method for manufacturing a sulfide-based inorganic solid electrolyte material according to the second embodiment includes, in addition to the step of obtaining a phosphorus sulfide composition using the method for manufacturing a phosphorus sulfide composition according to the second embodiment, the following step (A), and may further include step (B) and step (C). Step (C) may be carried out between step (A) and step (B), or may be carried out after step (B).

[0175] Step (A): A step of subjecting a raw material composition of a sulfide-based inorganic solid electrolyte material containing lithium sulfide and a phosphorus sulfide composition obtained by the method for manufacturing a phosphorus sulfide composition according to the second embodiment to mechanical treatment to cause a chemical reaction among the components while vitrifying to obtain a glassy sulfide-based inorganic solid electrolyte material.

[0176] Step (B): A step of heating the obtained glassy sulfide-based inorganic solid electrolyte material to crystallize at least a part thereof to obtain a glass-ceramic state sulfide-based inorganic solid electrolyte material.

[0177] Step (C): A step of pulverizing, classifying, or granulating the obtained glass or glass-ceramic state sulfide-based inorganic solid electrolyte material

[0178] (Process (A))

[0179] First, prepare a raw material composition for a sulfide-based inorganic solid electrolyte material. The raw material composition for the sulfide-based inorganic solid electrolyte material contains lithium sulfide and a phosphorus sulfide composition obtained by the manufacturing method of the phosphorus sulfide composition of the second embodiment. Optionally, lithium nitride may also be included.

[0180] Here, adjust the mixing ratio of each raw material in the raw material composition so that the obtained sulfide-based inorganic solid electrolyte material has a desired composition ratio.

[0181] In addition, the preferred mode of Process (A) in the manufacturing method of the sulfide-based inorganic solid electrolyte material of the second embodiment is the same as the preferred mode of Process (A) in the manufacturing method of the sulfide-based inorganic solid electrolyte material of the first embodiment. Also, the preferred modes of lithium sulfide and lithium nitride used as raw materials are the same as the preferred modes of lithium sulfide and lithium nitride in the manufacturing method of the sulfide-based inorganic solid electrolyte material of the first embodiment.

[0182] The preferred modes of Process (B) and Process (C) in the manufacturing method of the sulfide-based inorganic solid electrolyte material of the second embodiment are the same as the preferred modes of Process (B) and Process (C) in the manufacturing method of the sulfide-based inorganic solid electrolyte material of the first embodiment.

[0183] [Sulfide-based inorganic solid electrolyte material]

[0184] The sulfide-based inorganic solid electrolyte material of the second embodiment can be obtained by the manufacturing method of the sulfide-based inorganic solid electrolyte material of the second embodiment.

[0185] The preferred mode of the sulfide-based inorganic solid electrolyte material of the second embodiment is the same as the preferred mode of the sulfide-based inorganic solid electrolyte material of the first embodiment.

[0186] <Third Embodiment>

[0187] The phosphorus sulfide composition, the manufacturing method of the sulfide-based inorganic solid electrolyte material, and the sulfide-based inorganic solid electrolyte material of the third embodiment will be described.

[0188] [Phosphorus sulfide composition]

[0189] The phosphorus sulfide composition of the third embodiment is a phosphorus sulfide composition for a sulfide-based inorganic solid electrolyte material containing at least P2S5 and P4S9. When the total content of P2S5, P4S9, P4S7, and P4S3 in the phosphorus sulfide composition is set to 100% by mass, according to the solid 31The content of P2S5 calculated by 31P-NMR spectroscopy is 30% by mass or more and 60% by mass or less, and the crystallinity calculated from the spectrum obtained by X-ray diffraction using CuKα rays as the radiation source is 40% or more and 70% or less.

[0190] According to the research by the present inventors, it has been clarified that if the type of phosphorus sulfide (for example, manufacturing company, manufacturing batch, manufacturing method), which is one of the raw materials of the sulfide-based inorganic solid electrolyte material, is changed, the lithium ion conductivity of the obtained sulfide-based inorganic solid electrolyte material sometimes becomes low.

[0191] Therefore, the present inventors have intensively studied to provide a manufacturing method for stably obtaining a sulfide-based inorganic solid electrolyte material with improved lithium ion conductivity. As a result, it has been found that if a phosphorus sulfide composition in which the content of P2S5 calculated from 31P-NMR spectroscopy and the crystallinity calculated from the spectrum obtained by X-ray diffraction using CuKα rays as the radiation source are within specific ranges is used as the raw material when manufacturing the sulfide-based inorganic solid electrolyte material, the lithium ion conductivity of the obtained sulfide-based inorganic solid electrolyte material can be improved, and thus the present invention has been completed. 31 That is, according to the third embodiment, as the raw material of the sulfide-based inorganic solid electrolyte material, a phosphorus sulfide composition in which the content of P2S5 calculated from 31P-NMR spectroscopy is 30% by mass or more and 60% by mass or less and the crystallinity calculated from the spectrum obtained by X-ray diffraction using CuKα rays as the radiation source is 40% or more and 70% or less is used, and a sulfide-based inorganic solid electrolyte material with improved lithium ion conductivity can be stably obtained.

[0192] That is, according to the third embodiment, as the raw material of the sulfide-based inorganic solid electrolyte material, a phosphorus sulfide composition in which the content of P2S5 calculated from 31P-NMR spectroscopy is 30% by mass or more and 60% by mass or less and the crystallinity calculated from the spectrum obtained by X-ray diffraction using CuKα rays as the radiation source is 40% or more and 70% or less is used, and a sulfide-based inorganic solid electrolyte material with improved lithium ion conductivity can be stably obtained. 31 That is, according to the third embodiment, as the raw material of the sulfide-based inorganic solid electrolyte material, a phosphorus sulfide composition in which the content of P2S5 calculated from 31P-NMR spectroscopy is 30% by mass or more and 60% by mass or less and the crystallinity calculated from the spectrum obtained by X-ray diffraction using CuKα rays as the radiation source is 40% or more and 70% or less is used, and a sulfide-based inorganic solid electrolyte material with improved lithium ion conductivity can be stably obtained.

[0193] The content of P2S5 in the phosphorus sulfide composition of the third embodiment is 30% by mass or more and 60% by mass or less. From the viewpoint of further improving the lithium ion conductivity of the sulfide-based inorganic solid electrolyte material of the third embodiment, when the total amount of the phosphorus sulfide composition of the third embodiment is set to 100% by mass, it is preferably 35% by mass or more, more preferably 38% by mass or more, further preferably 40% by mass or more, and preferably 55% by mass or less, more preferably 52% by mass or less, further preferably 50% by mass or less.

[0194] Here, the content of P2S5 in the phosphorus sulfide composition of the third embodiment can be calculated from 31P-NMR spectroscopy. 31 Calculated by 31P-NMR spectroscopy.

[0195] From the viewpoint of further improving the lithium ion conductivity of the sulfide-based inorganic solid electrolyte material of the third embodiment, when the total amount of the phosphorus sulfide composition of the third embodiment is set to 100% by mass, the content of P4S9 in the phosphorus sulfide composition of the third embodiment is preferably 40% by mass or more, more preferably 45% by mass or more, further preferably 48% by mass or more, still further preferably 50% by mass or more, and preferably 70% by mass or less, more preferably 65% by mass or less, further preferably 62% by mass or less, still further preferably 60% by mass or less.

[0196] Here, the content of P4S9 in the phosphorus sulfide composition of the third embodiment can be calculated from the solid 31 P-NMR spectrum.

[0197] The phosphorus sulfide composition of the third embodiment contains at least P2S5 and P4S9. From the viewpoint of further improving the lithium ion conductivity of the sulfide-based inorganic solid electrolyte material of the third embodiment, when the total amount of the phosphorus sulfide composition of the third embodiment is set to 100% by mass, the total content of P2S5 and P4S9 in the phosphorus sulfide composition of the third embodiment is preferably 90% by mass or more, more preferably 95% by mass or more, further preferably 97% by mass or more, still further preferably 98% by mass or more, still further preferably 99% by mass or more. The upper limit of the total content of P2S5 and P4S9 in the phosphorus sulfide composition of the third embodiment is not particularly limited, for example, it is 100% by mass or less.

[0198] Solid 31 The solid P-NMR spectrum can be measured, for example, by the following method.

[0199] First, in a glove box purged with N2 gas, a test sample is filled in a measurement sample tube with a diameter of 3.2 mm, and it is rotated in a state inclined at the magic angle (54.7 degrees) with respect to the external magnetic field (Magic Angle Spining: MAS, magic angle rotation), and the measurement is carried out under the following conditions.

[0200] Apparatus: JNM-ECA-600 manufactured by JEOL Resonance Inc.

[0201] Observation frequency: 242.95 MHz.

[0202] Pulse width: 90° pulse.

[0203] Pulse delay time: 2800 seconds.

[0204] Number of integration operations: 64 times.

[0205] Measurement mode: single pulse method.

[0206] Magic angle spinning (MAS) speed: 12 kHz.

[0207] Standard substance: (NH4)2HPO4·1.33 ppm.

[0208] For the peaks detected in the 31 P-NMR spectrum of the test sample, referring to Reference 1 "Hellmut Eckert, Cheryl S. Liang and Galen D. Stucky: 31 P magic angle spinning NMR of crystalline phosphorous sulfides. Correlation of 31 P chemical shielding tensors with local environments, J. Phys. Chem, 1989, 93, 452-457", waveform separation using a Gaussian function was performed based on the following peak assignments, and the integral value of each peak was calculated. The integral value of the peak from each component is proportional to the molar number of phosphorus contained. Therefore, the content ratio can be calculated based on the obtained integral value and the molecular weight of each component.

[0209] The chemical shift of P2S5 is 40 - 52 ppm, the chemical shift of P4S9 is 52 - 70 ppm, the chemical shifts of P4S7 are 80 - 90 ppm, 90 - 100 ppm, 110 - 115 ppm, and the chemical shifts of P4S3 are 80 - 90 ppm, 90 - 100 ppm.

[0210] The crystallinity of the phosphorous sulfide composition of the third embodiment calculated from the spectrum obtained by X-ray diffraction using CuKα rays as the radiation source is 40% or more and 70% or less. From the viewpoint of further improving the lithium ion conductivity of the sulfide-based inorganic solid electrolyte material of the third embodiment, it is preferably 45% or more, more preferably 48% or more, further preferably 50% or more, further preferably 52% or more, and preferably 65% or less, more preferably 63% or less, further preferably 60% or less.

[0211] Here, referring to Figure 4 The method for calculating the crystallinity of the phosphorous sulfide composition is described. Figure 4 It is a diagram showing the X-ray diffraction spectrum for explaining the method for calculating the crystallinity (peak separation method) of the phosphorous sulfide composition of the third embodiment.

[0212] First, in X-ray diffraction using CuKα rays as the radiation source, the diffraction curve corresponding to the crystalline material is a sharp peak, and the diffraction curve corresponding to the amorphous material becomes a broad halo due to scattering. Therefore, the proportion of the crystalline material relative to the total of the crystalline and amorphous materials can be calculated as the degree of crystallinity.

[0213] In the third embodiment, as a method for calculating the degree of crystallinity, the peak separation method is used. Without considering the effects of non-interference scattering, lattice disorder, etc., the peaks are separated into crystalline diffraction curves and amorphous halos in the X-ray diffraction pattern (also called the scattering curve) using the profile fitting method. The analysis software attached to the X-ray diffractometer can be used in the profile fitting.

[0214] The specific steps for calculating the degree of crystallinity are as follows (refer to Figure 4 ; cited from "X-ray Diffraction Handbook" of Rigaku Corporation (February 21, 2000, third edition, P83, Figure 3 .6.2)).

[0215] (1) Separation of background

[0216] Connect the X-ray intensities from the low-angle side to the high-angle side with a straight line, and use the area under the straight line as the background.

[0217] (2) Separation of halos

[0218] Estimate the halo pattern caused by the amorphous material, and separate the halos from the scattering curve after subtracting the background.

[0219] (3) Separation of crystalline diffraction curves

[0220] Separate the crystalline diffraction curves by the same method as in (2) above.

[0221] (4) Calculation of the degree of crystallinity

[0222] Using the areas under the curves (integrated intensities) of the diffraction curves of the amorphous component (amorphous halos) and the crystalline component (crystalline diffraction curves) separated from the scattering curve, calculate the degree of crystallinity according to the following formula (1).

[0223] Xc = {Ic / (Ic + Ia)} × 100 (1)

[0224] Ic: Area under the curve (integrated intensity) of the diffraction curve of the crystalline component (crystalline diffraction curve).

[0225] Ia: Area under the curve (integrated intensity) of the diffraction curve of the amorphous component (amorphous halos).

[0226] In addition, when the phosphorus sulfide composition contains a solvent, it is preferably measured after drying and removing the solvent from the phosphorus sulfide composition.

[0227] From the viewpoint of further improving the lithium ion conductivity of the sulfide-based inorganic solid electrolyte material of the third embodiment, it is preferable that in the DSC curve of the phosphorus sulfide composition of the third embodiment obtained by measurement with a differential scanning calorimeter, an endothermic peak is observed in the temperature range of 280 °C or higher and 300 °C or lower. The heat of fusion of the endothermic peak is preferably 60 J / g or more, more preferably 65 J / g or more, further preferably 70 J / g or more, further preferably 75 J / g or more, further preferably 80 J / g or more, and preferably 90 J / g or less, more preferably 88 J / g or less, further preferably 85 J / g or less.

[0228] In addition, the above DSC curve can be measured by the following method, for example.

[0229] First, in an argon atmosphere, 20 to 25 mg of the phosphorus sulfide composition is weighed and placed in an aluminum pan, and then the aluminum lid is covered and sealed with a sample sealer. The reference aluminum container is in an empty state. Differential scanning calorimetry is performed using a differential scanning calorimeter under the environmental conditions of a starting temperature of 25 °C, a measurement temperature range of 30 to 350 °C, a heating rate of 5 °C / min, and an argon atmosphere of 100 mL per minute. In addition, there is no particular limitation on the differential scanning calorimeter. For example, DSC6300 manufactured by Seiko Instruments Inc. can be used.

[0230] In addition, when the phosphorus sulfide composition contains a solvent, it is preferably measured after drying and removing the solvent from the phosphorus sulfide composition.

[0231] Based on the DSC curve thus obtained, the presence or absence of an endothermic peak can be observed in the temperature range of 280 °C or higher and 300 °C or lower.

[0232] Here, the heat of fusion of the above endothermic peak is calculated by obtaining the area enclosed by the endothermic melting curve including the endothermic peak and the baseline. Since the heat capacity inherent to the substance is different before and after the thermal change, the baseline before and after the endothermic peak is not a straight line.

[0233] Therefore, in the present embodiment, the baseline in the endothermic peak is Figure 5 the line connecting point R and point S shown. Point R is the intersection point of the line parallel to the Y-axis passing through the intersection point P of the baseline before the endothermic peak and the tangent of the endothermic peak and the endothermic melting curve. Point S is the intersection point of the line parallel to the Y-axis passing through the intersection point Q of the baseline after the endothermic peak and the tangent of the endothermic peak and the endothermic melting curve.

[0234] The properties of the phosphorus sulfide composition as the third embodiment, for example, can be exemplified by a powdery form. Since the production of the sulfide-based inorganic solid electrolyte material of the third embodiment is usually carried out dry, if the properties of the phosphorus sulfide composition of the third embodiment are in a powdery form, it is easier to produce the sulfide-based inorganic solid electrolyte material.

[0235] [Manufacturing Method of Sulfide-Based Inorganic Solid Electrolyte Material]

[0236] The manufacturing method of the sulfide-based inorganic solid electrolyte material of the third embodiment includes a step of obtaining a glassy sulfide-based inorganic solid electrolyte material by subjecting a raw material composition of the sulfide-based inorganic solid electrolyte material containing the phosphorus sulfide composition and lithium sulfide of the third embodiment to mechanical treatment to cause a chemical reaction among the components while vitrifying.

[0237] That is, the manufacturing method of the sulfide-based inorganic solid electrolyte material of the third embodiment includes the following step (A), and may further include step (B) and step (C). Step (C) can be carried out between step (A) and step (B), or can be carried out after step (B).

[0238] Step (A): A step of obtaining a glassy sulfide-based inorganic solid electrolyte material by subjecting a raw material composition of the sulfide-based inorganic solid electrolyte material containing the phosphorus sulfide composition and lithium sulfide of the third embodiment to mechanical treatment to cause a chemical reaction among the components while vitrifying.

[0239] Step (B): A step of heating the obtained glassy sulfide-based inorganic solid electrolyte material to crystallize at least a part thereof to obtain a glass-ceramic state sulfide-based inorganic solid electrolyte material.

[0240] Step (C): A step of pulverizing, classifying or granulating the obtained glass or glass-ceramic state sulfide-based inorganic solid electrolyte material.

[0241] (Step (A))

[0242] First, prepare a raw material composition of the sulfide-based inorganic solid electrolyte material. The raw material composition of the sulfide-based inorganic solid electrolyte material contains the phosphorus sulfide composition and lithium sulfide of the third embodiment, and may further contain lithium nitride as needed.

[0243] Here, adjust the mixing ratio of each raw material in the raw material composition so that the obtained sulfide-based inorganic solid electrolyte material has a desired composition ratio.

[0244] In addition, the preferred embodiment of step (A) in the manufacturing method of the sulfide-based inorganic solid electrolyte material of the third embodiment is the same as that of step (A) in the manufacturing method of the sulfide-based inorganic solid electrolyte material of the first embodiment. Also, the preferred embodiments of lithium sulfide and lithium nitride used as raw materials are the same as those of lithium sulfide and lithium nitride in the manufacturing method of the sulfide-based inorganic solid electrolyte material of the first embodiment.

[0245] The preferred embodiments of step (B) and step (C) in the manufacturing method of the sulfide-based inorganic solid electrolyte material of the third embodiment are the same as those of step (B) and step (C) in the manufacturing method of the sulfide-based inorganic solid electrolyte material of the first embodiment.

[0246] [Sulfide-based inorganic solid electrolyte material]

[0247] The sulfide-based inorganic solid electrolyte material of the third embodiment can be obtained by the manufacturing method of the sulfide-based inorganic solid electrolyte material of the third embodiment. That is, the sulfide-based inorganic solid electrolyte material of the third embodiment contains the mechanically treated product of the raw material composition of the sulfide-based inorganic solid electrolyte material of the third embodiment.

[0248] The preferred embodiment of the sulfide-based inorganic solid electrolyte material of the third embodiment is the same as that of the sulfide-based inorganic solid electrolyte material of the first embodiment.

[0249] [Sulfide-based inorganic solid electrolyte]

[0250] The sulfide-based inorganic solid electrolyte of this embodiment contains the sulfide-based inorganic solid electrolyte material of this embodiment.

[0251] For the sulfide-based inorganic solid electrolyte of this embodiment, as components other than the sulfide-based inorganic solid electrolyte material of this embodiment, for example, within the scope of not impairing the object of the present invention, it may contain a solid electrolyte material of a different type from the sulfide-based inorganic solid electrolyte material of this embodiment.

[0252] As a solid electrolyte material of a different type from the sulfide-based inorganic solid electrolyte material of this embodiment, as long as it has ion conductivity and insulation, there is no particular limitation, and generally, materials used for lithium ion batteries can be used. For example, inorganic solid electrolyte materials such as sulfide-based inorganic solid electrolyte materials of different types from the sulfide-based inorganic solid electrolyte material of this embodiment, oxide-based inorganic solid electrolyte materials, and other lithium-based inorganic solid electrolyte materials can be cited; organic solid electrolyte materials such as polymer electrolytes.

[0253] As sulfide-based inorganic solid electrolyte materials different from those of the present embodiment, for example, Li2S-SiS2 materials, Li2S-GeS2 materials, Li2S-Al2S3 materials, Li2S-SiS2-Li3PO4 materials, etc. can be cited. They can be used alone or in combination of two or more.

[0254] Here, for example, the Li2S-SiS2 material refers to a solid electrolyte material obtained by subjecting an inorganic composition containing at least Li2S (lithium sulfide) and SiS2 to a chemical reaction with each other by mechanical treatment.

[0255] Here, lithium sulfide also includes polysulfide lithium.

[0256] As oxide-based inorganic solid electrolyte materials, for example, sodium superionic conductor type materials (NASICON type materials) such as LiTi2(PO4)3, LiZr2(PO4)3, LiGe2(PO4)3, etc.; perovskite type materials such as (La 0.5+x Li 0.5-3x )TiO3; Li2O-P2O5 materials; Li2O-P2O5-Li3N materials; etc.

[0257] As other lithium-based inorganic solid electrolyte materials, for example, LiPON, LiNbO3, LiTaO3, Li3PO4, LiPO 4-x N x (where x is 0 < x ≤ 1), LiN, LiI, lithium superionic conductor (LISICON), etc.

[0258] Furthermore, glass ceramics obtained by crystallizing an inorganic solid electrolyte can also be used as an inorganic solid electrolyte material.

[0259] As the above-mentioned organic solid electrolyte materials, for example, dry polymer electrolytes, gel electrolytes and other polymer electrolytes can be used.

[0260] As polymer electrolytes, polymer electrolytes commonly used in lithium ion batteries can be used.

[0261] [Sulfide-based inorganic solid electrolyte film]

[0262] The sulfide-based inorganic solid electrolyte film of the present embodiment contains the sulfide-based inorganic solid electrolyte of the present embodiment as a main component.

[0263] The sulfide-based inorganic solid electrolyte membrane of the present embodiment is used, for example, to form a solid electrolyte layer of an all-solid-state lithium-ion battery. As an example of an all-solid-state lithium-ion battery using the solid electrolyte membrane of the present embodiment, a battery in which a positive electrode, a solid electrolyte layer, and a negative electrode are laminated in this order can be cited. In this case, the solid electrolyte layer is composed of the solid electrolyte membrane.

[0264] From the viewpoint of further suppressing the loss of the solid electrolyte and the generation of cracks on the surface of the solid electrolyte membrane, the average thickness of the sulfide-based inorganic solid electrolyte membrane of the present embodiment is preferably 5 μm or more, more preferably 10 μm or more, and further preferably 20 μm or more.

[0265] The average thickness of the sulfide-based inorganic solid electrolyte membrane of the present embodiment is preferably 500 μm or less, more preferably 200 μm or less, and further preferably 100 μm or less. Thereby, the impedance of the solid electrolyte membrane can be further reduced, and as a result, the battery characteristics of the obtained all-solid-state lithium-ion battery can be further improved.

[0266] The sulfide-based inorganic solid electrolyte membrane of the present embodiment is preferably a compression molded body of particulate solid electrolyte. That is, preferably, particulate solid electrolyte is compressed to form a solid electrolyte membrane having a predetermined strength due to the anchoring effect between the solid electrolyte materials. By forming a compression molded body, the solid electrolytes are bonded to each other, and the strength of the obtained solid electrolyte membrane is further improved. As a result, the loss of the solid electrolyte and the generation of cracks on the surface of the solid electrolyte membrane can be further suppressed.

[0267] The content of the sulfide-based inorganic solid electrolyte material of the present embodiment in the sulfide-based inorganic solid electrolyte membrane of the present embodiment is preferably 50% by mass or more, more preferably 60% by mass or more, further preferably 70% by mass or more, further preferably 80% by mass or more, and further preferably 90% by mass or more. Thereby, the contact property between the solid electrolytes can be improved, and the interfacial contact resistance of the solid electrolyte membrane can be reduced. As a result, the lithium ion conductivity of the solid electrolyte membrane is further improved. Moreover, by using such a solid electrolyte membrane having excellent lithium ion conductivity, the battery characteristics of the obtained all-solid-state lithium-ion battery can be further improved.

[0268] The upper limit of the content of the sulfide-based inorganic solid electrolyte material of the present embodiment in the sulfide-based inorganic solid electrolyte membrane of the present embodiment is not particularly limited, and is, for example, 100% by mass or less.

[0269] The planar shape of the sulfide-based inorganic solid electrolyte membrane of the present embodiment is not particularly limited, and can be appropriately selected according to the shapes of the electrodes and current collectors. For example, it can be rectangular.

[0270] In the sulfide-based inorganic solid electrolyte film of the present embodiment, a binder resin may be included. The content of the binder resin is preferably less than 0.5% by mass, more preferably less than 0.1% by mass, further preferably less than 0.05% by mass, and further preferably less than 0.01% by mass. Additionally, it is further preferred that the solid electrolyte film of the present embodiment substantially does not contain a binder resin, and more preferably does not contain a binder resin. Thereby, the contact between solid electrolytes can be improved, and the interfacial contact resistance of the solid electrolyte film can be reduced. As a result, the lithium ion conductivity of the solid electrolyte film can be further enhanced. Moreover, by using such a solid electrolyte film with improved lithium ion conductivity, the battery characteristics of the obtained all-solid-state lithium ion battery can be improved.

[0271] It should be noted that "substantially does not contain a binder resin" means that it may contain to the extent that the effects of the present embodiment are not impaired. Additionally, when an adhesive resin layer is provided between the solid electrolyte layer and the positive electrode or the negative electrode, the adhesive resin from the adhesive resin layer present near the interface between the solid electrolyte layer and the adhesive resin layer is excluded from the "binder resin in the solid electrolyte film".

[0272] The above-mentioned binder resin refers to a binder commonly used in lithium ion batteries for bonding inorganic solid electrolyte materials. For example, polyvinyl alcohol, polyacrylic acid, carboxymethyl cellulose, polytetrafluoroethylene, polyvinylidene fluoride, styrene-butadiene rubber, polyimide, etc. can be cited.

[0273] For example, by stacking particulate solid electrolytes in a film shape on the surface of the cavity of a mold or on the surface of a substrate, and then pressing the solid electrolytes stacked in a film shape, the sulfide-based inorganic solid electrolyte film of the present embodiment can be obtained.

[0274] The method of pressing the above-mentioned solid electrolyte is not particularly limited. For example, when particulate solid electrolytes are stacked on the surface of the cavity of a mold, pressing using a mold and a press die can be used; when particulate solid electrolytes are stacked on the surface of a substrate, pressing using a mold and a press die, roll pressing, flat pressing, etc. can be used.

[0275] The pressure for pressing the solid electrolyte is, for example, 10 MPa or more and 500 MPa or less.

[0276] Additionally, if necessary, heating can also be performed simultaneously while pressing the inorganic solid electrolytes stacked in a film shape. As long as heat pressing is performed, fusion and bonding between the solid electrolytes will occur, and the strength of the obtained solid electrolyte film will be further improved. As a result, the loss of solid electrolytes and the generation of cracks on the surface of the solid electrolyte film can be further suppressed.

[0277] The temperature for heating the solid electrolyte is, for example, 40°C or higher and 500°C or lower.

[0278] [Lithium-ion battery]

[0279] The lithium-ion battery of the present embodiment is, for example, a lithium-ion battery including a positive electrode having a positive electrode active material layer, an electrolyte layer, and a negative electrode having a negative electrode active material layer, and at least one of the positive electrode active material layer, the electrolyte layer, and the negative electrode active material layer contains the sulfide-based inorganic solid electrolyte material of the present embodiment.

[0280] Figure 1 It is a cross-sectional view showing an example of the structure of the lithium-ion battery of the present embodiment.

[0281] The lithium-ion battery 100 of the present embodiment includes, for example, a positive electrode 110 having a positive electrode active material layer 101, an electrolyte layer 120, and a negative electrode 130 having a negative electrode active material layer 103.

[0282] Moreover, at least one of the positive electrode active material layer 101, the negative electrode active material layer 103, and the electrolyte layer 120 contains the above-mentioned sulfide-based inorganic solid electrolyte material of the present embodiment. Additionally, it is preferable that all of the positive electrode active material layer 101, the negative electrode active material layer 103, and the electrolyte layer 120 contain the above-mentioned sulfide-based inorganic solid electrolyte material of the present embodiment.

[0283] It should be noted that, in the present embodiment, unless otherwise specified, the layer containing the positive electrode active material is referred to as the positive electrode active material layer 101. As needed, the positive electrode 110 may include a current collector 105 in addition to the positive electrode active material layer 101, or may not include the current collector 105. Additionally, in the present embodiment, unless otherwise specified, the layer containing the negative electrode active material is referred to as the negative electrode active material layer 103. As needed, the negative electrode 130 may include a current collector 105 in addition to the negative electrode active material layer 103, or may not include the current collector 105.

[0284] The shape of the lithium-ion battery 100 of the present embodiment is not particularly limited, and examples include cylindrical, coin-shaped, rectangular, film-shaped, and any other shape.

[0285] The lithium-ion battery 100 of the present embodiment is manufactured by a generally well-known method. For example, the positive electrode 110, the electrolyte layer 120, and the negative electrode 130 are stacked to form a cylindrical, coin-shaped, rectangular, film-shaped, or any other shape, and as needed, it is fabricated by enclosing a non-aqueous electrolyte.

[0286] <Positive electrode>

[0287] The positive electrode 110 is not particularly limited and can be a positive electrode commonly used in lithium-ion batteries. The positive electrode 110 is not particularly limited and can be manufactured by a generally well-known method. For example, it can be obtained by forming a positive electrode active material layer 101 containing a positive electrode active material on the surface of a current collector 105 such as an aluminum foil.

[0288] The thickness and density of the positive electrode active material layer 101 are appropriately determined according to the usage of the battery, etc., and thus are not particularly limited and can be set according to generally well-known information.

[0289] The positive electrode active material layer 101 contains a positive electrode active material.

[0290] As the positive electrode active material, any positive electrode active material that can be used in the positive electrode of a lithium-ion battery can be used without particular limitation. For example, lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMn2O4), solid solution oxide (Li2MnO3-LiMO2 (M = Co, Ni, etc.)), lithium-manganese-nickel oxide (LiNi 1 / 3 Mn 1 / 3 Co 1 / 3O2), olivine-type lithium phosphate oxide (LiFePO4) and other composite oxides; conductive polymers such as polyaniline and polypyrrole; sulfide-based positive electrode active materials such as Li2S, CuS, Li-Cu-S compounds, TiS2, FeS, MoS2, Li-Mo-S compounds, Li-Ti-S compounds, Li-V-S compounds, Li-Fe-S compounds; materials with sulfur as the active material such as sulfur-impregnated acetylene black, sulfur-impregnated porous carbon, and mixed powder of sulfur and carbon; etc.

[0291] The positive electrode active material layer 101 is not particularly limited. As components other than the above positive electrode active material, for example, it may also contain one or more materials selected from binder resins, thickeners, conductive aids, solid electrolyte materials, etc. Hereinafter, each material will be described.

[0292] The positive electrode active material layer 101 may contain a binder resin having the function of bonding the positive electrode active materials to each other and bonding the positive electrode active material and the current collector 105.

[0293] As long as the binder resin of the present embodiment is a general binder resin that can be used in lithium-ion batteries, there is no particular limitation. For example, polyvinyl alcohol, polyacrylic acid, carboxymethyl cellulose, polytetrafluoroethylene, polyvinylidene fluoride, styrene-butadiene rubber, polyimide, etc. can be cited. These binders can be used alone or in combination of two or more.

[0294] From the viewpoint of ensuring the fluidity of the slurry suitable for coating, the positive electrode active material layer 101 may also contain a thickening agent. As the thickening agent, any common thickening agent that can be used in a lithium-ion battery may be used, and there is no particular limitation. For example, carboxymethyl cellulose, methyl cellulose, hydroxypropyl cellulose and other cellulose-based polymers and their ammonium salts and alkali metal salts, polycarboxylic acids, polyethylene oxide, polyvinylpyrrolidone, polyacrylate, polyvinyl alcohol and other water-soluble polymers can be cited. These thickening agents can be used alone or in combination of two or more.

[0295] From the viewpoint of improving the conductivity of the positive electrode 110, the positive electrode active material layer 101 may contain a conductive assistant. As the conductive assistant, any common conductive assistant that can be used in a lithium-ion battery may be used, and there is no particular limitation. For example, acetylene black, Ketjen black and other carbon blacks; carbon materials such as vapor-grown carbon fibers can be cited.

[0296] The positive electrode of the lithium-ion battery of the present embodiment may contain a solid electrolyte containing the sulfide-based inorganic solid electrolyte material of the present embodiment, or may contain a solid electrolyte containing a solid electrolyte material of a different type from the sulfide-based inorganic solid electrolyte material of the present embodiment.

[0297] As the solid electrolyte material of a different type from the sulfide-based inorganic solid electrolyte material of the present embodiment, as long as it has ion conductivity and insulation, there is no particular limitation, and materials generally used for lithium-ion batteries can usually be used. For example, sulfide-based inorganic solid electrolyte materials of different types from the sulfide-based inorganic solid electrolyte material of the present embodiment, oxide-based inorganic solid electrolyte materials, other lithium-based inorganic solid electrolyte materials and other inorganic solid electrolyte materials; organic solid electrolyte materials such as polymer electrolytes can be cited. More specifically, the solid electrolyte materials cited in the description of the sulfide-based inorganic solid electrolyte of the present embodiment above can be used.

[0298] The mixing ratio of various materials in the positive electrode active material layer 101 is appropriately determined according to the use purpose of the battery and the like, and therefore, there is no particular limitation, and it can be set according to generally known information.

[0299] <Negative electrode>

[0300] The negative electrode 130 is not particularly limited, and materials generally used for lithium-ion batteries can be used. The negative electrode 130 is not particularly limited, and it can be manufactured according to generally known methods. For example, it can be obtained by forming a negative electrode active material layer 103 containing a negative electrode active material on the surface of a current collector 105 such as copper.

[0301] The thickness and density of the negative electrode active material layer 103 are appropriately determined according to the usage of the battery and the like, and thus, there is no particular limitation and can be set according to generally known information.

[0302] The negative electrode active material layer 103 contains a negative electrode active material.

[0303] As the above-mentioned negative electrode active material, any ordinary negative electrode active material that can be used for the negative electrode of a lithium-ion battery can be used, and there is no particular limitation. For example, carbonaceous materials such as natural graphite, artificial graphite, resin carbon, carbon fiber, activated carbon, hard carbon, and soft carbon can be cited; metal-based materials mainly composed of lithium, lithium alloy, tin, tin alloy, silicon, silicon alloy, gallium, gallium alloy, indium, indium alloy, aluminum, aluminum alloy, etc.; conductive polymers such as polyacene, polyacetylene, and polypyrrole; lithium titanium composite oxides (such as Li4Ti5O 12 ) etc. These negative electrode active materials can be used alone or in combination of two or more.

[0304] There is no particular limitation on the negative electrode active material layer 103. As components other than the above-mentioned negative electrode active material, for example, one or more materials selected from binder resins, thickeners, conductive aids, solid electrolyte materials, etc. can also be included. As these materials, there is no particular limitation, and for example, materials the same as those used in the above-mentioned positive electrode 110 can be cited.

[0305] Since the mixing ratio of various materials in the negative electrode active material layer 103 is appropriately determined according to the usage of the battery and the like, there is no particular limitation and can be set according to generally known information.

[0306] The negative electrode of the lithium-ion battery of the present embodiment may contain a solid electrolyte containing the sulfide-based inorganic solid electrolyte material of the present embodiment, or may contain a solid electrolyte containing a solid electrolyte material of a different type from the sulfide-based inorganic solid electrolyte material of the present embodiment.

[0307] As a solid electrolyte material of a different type from the sulfide-based inorganic solid electrolyte material of the present embodiment, as long as it has ion conductivity and insulation, there is no particular limitation, and materials generally used for lithium-ion batteries can be used. For example, inorganic solid electrolyte materials such as sulfide-based inorganic solid electrolyte materials of different types from the sulfide-based inorganic solid electrolyte material of the present embodiment, oxide-based inorganic solid electrolyte materials, and other lithium-based inorganic solid electrolyte materials can be cited; organic solid electrolyte materials such as polymer electrolytes. More specifically, the solid electrolyte materials cited in the description of the sulfide-based inorganic solid electrolyte of the present embodiment above can be used.

[0308] <Electrolyte layer>

[0309] Next, the electrolyte layer 120 will be described. The electrolyte layer 120 is a layer formed between the positive electrode active material layer 101 and the negative electrode active material layer 103.

[0310] Examples of the electrolyte layer 120 include a layer formed by impregnating a separator with a non-aqueous electrolyte and a solid electrolyte layer containing a solid electrolyte.

[0311] As the separator of the present embodiment, any separator that electrically insulates the positive electrode 110 and the negative electrode 130 and has a function of allowing lithium ions to pass through can be used, and there is no particular limitation. For example, a porous membrane can be used.

[0312] As the porous membrane, a microporous polymer membrane is preferably used, and examples of the material include polyolefin, polyimide, polyvinylidene fluoride, polyester, etc. In particular, a porous polyolefin membrane is preferably used. Specifically, a porous polyethylene membrane, a porous polypropylene membrane, etc. can be cited.

[0313] The above non-aqueous electrolyte is obtained by dissolving an electrolyte in a solvent.

[0314] As the above electrolyte, a known lithium salt can be arbitrarily used as long as it is selected according to the type of the active material. For example, LiClO4, LiBF6, LiPF6, LiCF3SO3, LiCF3CO2, LiAsF6, LiSbF6, LiB 10 Cl 10 , LiAlCl4, LiCl, LiBr, LiB(C2H5)4, CF3SO3Li, CH3SO3Li, LiCF3SO3, LiC4F9SO3, Li(CF3SO2)2N, lithium lower fatty acid carboxylate, etc.

[0315] As the solvent for dissolving the above electrolyte, any solvent that is commonly used as a liquid for dissolving the electrolyte may be used without particular limitation. Examples include carbonate esters such as ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (MEC), and vinylene carbonate (VC); lactones such as γ-butyrolactone and γ-valerolactone; ethers such as trimethoxymethane, 1,2-dimethoxyethane, diethyl ether, 2-ethoxyethane, tetrahydrofuran, and 2-methyltetrahydrofuran; sulfoxides such as dimethyl sulfoxide; oxolanes such as 1,3-dioxolane and 4-methyl-1,3-dioxolane; nitrogen-containing compounds such as acetonitrile, nitromethane, formamide, and dimethylformamide; organic acid esters such as methyl formate, methyl acetate, ethyl acetate, butyl acetate, methyl propionate, and ethyl propionate; phosphate triesters and diglyme; triglyme; sulfolanes such as sulfolane and methylsulfolane; oxazolidinones such as 3-methyl-2-oxazolidinone; sultones such as 1,3-propane sultone, 1,4-butane sultone, and naphthalene sulfonic acid lactone; and the like. They can be used alone or in combination of two or more.

[0316] The solid electrolyte layer of the present embodiment is a layer formed between the positive electrode active material layer 101 and the negative electrode active material layer 103, and is a layer formed of a solid electrolyte containing a solid electrolyte material. The solid electrolyte contained in the solid electrolyte layer only needs to have lithium ion conductivity without particular limitation. However, in the present embodiment, a solid electrolyte containing the sulfide-based inorganic solid electrolyte material of the present embodiment is preferred.

[0317] Regarding the content of the solid electrolyte contained in the solid electrolyte layer of the lithium ion battery of the present embodiment, any proportion that can obtain the desired insulation can be used without particular limitation. It is preferably 10% by volume or more and 100% by volume or less, more preferably 50% by volume or more and 100% by volume or less, still more preferably 70% by volume or more and 100% by volume or less, and even more preferably substantially free of components other than the solid electrolyte.

[0318] It should be noted that "substantially free of components other than the solid electrolyte" means that components other than the solid electrolyte may be contained to the extent that the effects of the present embodiment are not impaired.

[0319] The solid electrolyte contained in the solid electrolyte layer of the lithium ion battery of the present embodiment only needs to have lithium ion conductivity without particular limitation, and is preferably the sulfide-based inorganic solid electrolyte of the present embodiment.

[0320] Regarding the content of the sulfide-based inorganic solid electrolyte of the present embodiment contained in the solid electrolyte layer of the lithium-ion battery of the present embodiment, as long as it is a proportion capable of obtaining the desired insulation property, there is no particular limitation, and it is preferably 10% by volume or more and 100% by volume or less, more preferably 50% by volume or more and 100% by volume or less, further preferably 70% by volume or more and 100% by volume or less, further preferably 90% by volume or more and 100% by volume or less. Further preferably, it substantially does not contain components other than the sulfide-based inorganic solid electrolyte of the present embodiment.

[0321] It should be noted that "substantially does not contain components other than the sulfide-based inorganic solid electrolyte of the present embodiment" means that components other than the sulfide-based inorganic solid electrolyte of the present embodiment may be contained to the extent that the effects of the present embodiment are not impaired.

[0322] The solid electrolyte layer of the lithium-ion battery of the present embodiment may also contain an adhesive resin. By containing the adhesive resin, a flexible solid electrolyte layer can be obtained. As the adhesive resin, for example, fluorine-containing bonding materials such as polytetrafluoroethylene and polyvinylidene fluoride can be cited.

[0323] The thickness of the solid electrolyte layer of the lithium-ion battery of the present embodiment is preferably 0.1 μm or more and 1000 μm or less, more preferably 0.1 μm or more and 300 μm or less.

[0324] The above has described the embodiments of the present invention, but these are examples of the present invention, and various configurations other than the above can also be adopted.

[0325] It should be noted that the present invention is not limited to the foregoing embodiments, and modifications, improvements, etc. within the scope capable of achieving the object of the present invention are also included in the present invention.

[0326] Examples

[0327] Hereinafter, the present invention will be described by way of examples and comparative examples, but the present invention is not limited thereto.

[0328] [1] Measurement method

[0329] First, the measurement methods in the following examples and comparative examples will be described.

[0330] (1) Solid 31 P-NMR measurement

[0331] The phosphorus sulfide compositions used in the examples and comparative examples are respectively subjected to solid 31 P-NMR measurement as follows.

[0332] First, in a glove box purged with N2 gas, a test sample was filled in a measurement sample tube with a diameter of 3.2 mm, and it was rotated in a state inclined at the magic angle (54.7 degrees) with respect to the external magnetic field (Magic Angle Spining: MAS, magic angle rotation), and measurements were carried out under the following conditions.

[0333] Apparatus: JNM-ECA-600 manufactured by JEOL Resonance Inc.

[0334] Observation frequency: 242.95 MHz.

[0335] Pulse width: 90° pulse.

[0336] Pulse delay time: 2800 seconds.

[0337] Number of integration operations: 64 times.

[0338] Measurement mode: single pulse method.

[0339] Magic angle rotation (MAS) speed: 12 kHz.

[0340] Standard substance: (NH4)2HPO4·1.33 ppm.

[0341] For the peaks detected in the 31 P-NMR spectrum of the test sample, referring to Reference 1 "Hellmut Eckert, Cheryl S. Liang and Galen D. Stucky: 31 P magic angle spinning NMR of crystalline phosphorous sulfides. Correlation of 31 P chemical shielding tensors with local environments, J. Phys. Chem, 1989, 93, 452-457", waveform separation using a Gaussian function was carried out based on the following peak assignments, and the integral values of each peak were calculated. The content ratios were calculated based on the obtained integral values and the molecular weights of each component.

[0342] The chemical shift of P2S5 is 40 - 52 ppm, the chemical shift of P4S9 is 52 - 70 ppm, the chemical shift of P4S7 is 80 - 90 ppm, 90 - 100 ppm, 110 - 115 ppm, and the chemical shift of P4S3 is 80 - 90 ppm, 90 - 100 ppm.

[0343] (2) Determination of the Composition Ratio of Sulfide-based Inorganic Solid Electrolyte Materials

[0344] Using an ICP emission spectroscopic analyzer (manufactured by Seiko Instruments Inc., model SPS3000), the mass percentages of Li, P, and S in the sulfide-based inorganic solid electrolyte materials obtained in the examples and comparative examples were determined by ICP emission spectroscopy, and the molar ratios of each element were calculated based on these results.

[0345] (3) Determination of Lithium Ion Conductivity

[0346] The lithium ion conductivities of the sulfide-based inorganic solid electrolyte materials obtained in the examples and comparative examples were determined by the following method. The results are shown in Table 1.

[0347] First, 110 mg of the sulfide-based inorganic solid electrolyte material was pressed under the conditions of 270 MPa for 10 minutes to obtain a disk-shaped specimen with a diameter of 9.5 mm and a thickness of 1 mm.

[0348] Then, using a potentiostat / galvanostat SP-300 manufactured by Bio-Logic Science Instruments, with a voltage application of 10 mV, a measurement frequency range of 0.1 Hz to 3 MHz, and a measurement temperature of 27 °C, and using a Li foil as the electrode, the lithium ion conductivity of the obtained disk-shaped specimen was measured by the AC impedance method.

[0349] (4) X-ray Diffraction Analysis

[0350] The X-ray diffraction analysis spectra of the phosphorus sulfide compositions used in the examples and comparative examples were measured by the following method.

[0351] Using an X-ray diffractometer (manufactured by Rigaku Corporation, model RINT2000), with a voltage of 40 kV, a current of 40 mA, a divergence slit of 1°, a longitudinal limit of the divergence slit of 10 mm, a scattering slit of 1°, a receiving slit of 0.3 mm, a measurement start angle of 3°, a measurement end angle of 90°, and a scanning speed of 0.2° / minute, using CuKα rays as the radiation source, and placing the phosphorus sulfide composition in an airtight specimen holder filled with argon, the X-ray diffraction analysis spectra of the phosphorus sulfide composition were obtained respectively.

[0352] Figure 2 The X-ray diffraction analysis spectra of the phosphorus sulfide compositions used in each example and comparative example are shown. In addition, Figure 3An enlarged view of the range of 2θ = 20 to 30° of the X-ray diffraction analysis spectrum of the phosphorus sulfide composition used in each example and comparative example is shown. In addition, the number of peaks in the range of 2θ = 22.5° or more and 24.5° or less in the X-ray diffraction analysis spectrum of the phosphorus sulfide composition used in the examples and comparative examples is shown in Table 1.

[0353] (5) Measurement of crystallinity

[0354] First, using an X-ray diffractometer (manufactured by Rigaku Corporation, Japan, RINT2000), under the conditions of a voltage of 40 kV, a current of 40 mA, a divergence slit of 1°, a longitudinal limit of the divergence slit of 10 mm, a scattering slit of 1°, a receiving slit of 0.3 mm, a measurement start angle of 3°, a measurement end angle of 90°, and a scanning speed of 0.2° / minute, using CuKα rays as the radiation source, the phosphorus sulfide composition was placed in an airtight sample holder filled with argon, and the X-ray diffraction analysis spectra of the phosphorus sulfide composition were obtained respectively.

[0355] Then, using the following peak separation method, based on the obtained X-ray diffraction spectrum, the crystallinity of the phosphorus sulfide composition used in the examples and comparative examples was calculated.

[0356] First, without considering the effects of non-interference scattering, lattice disorder, etc., the peak was separated into a crystalline diffraction curve and an amorphous halo in the X-ray diffraction pattern using the profile fitting method. In the profile fitting, the analysis software attached to the X-ray diffractometer (manufactured by Rigaku Corporation, Japan, product name: Comprehensive Powder X-ray Analysis Software PDXL Application Analysis (Crystallinity)) was used.

[0357] The specific steps for calculating the crystallinity are as follows (refer to Figure 4 ; cited from "X-ray Diffraction Handbook" of Rigaku Corporation (February 21, 2000, third edition, P83, Figure 3 .6.2)).

[0358] (1) Separation of background

[0359] Connect the X-ray intensity from the low-angle side to the high-angle side with a straight line, and use the area under the straight line as the background.

[0360] (2) Separation of halo

[0361] Presume the halo pattern caused by amorphous, and separate the halo from the scattering curve after subtracting the background.

[0362] (3) Separation of crystalline diffraction curve

[0363] Separate the crystalline diffraction curve by the same method as in (2) above.

[0364] (4) Calculation of crystallinity

[0365] Using the area under the curve (integrated intensity) of the diffraction curve of the amorphous component (amorphous halo) and the diffraction curve of the crystalline component (crystalline diffraction curve) separated from the scattering curve, the crystallinity is calculated according to the following formula (1).

[0366] Xc = {Ic / (Ic + Ia)} × 100 (1)

[0367] Ic: Area under the curve (integrated intensity) of the diffraction curve of the crystalline component (crystalline diffraction curve). Ia: Area under the curve (integrated intensity) of the diffraction curve of the amorphous component (amorphous halo).

[0368] (6) Measurement of heat of fusion

[0369] As described below, differential scanning calorimetry (DSC) measurements were performed on the phosphorus sulfide compositions used in the examples and comparative examples, respectively. First, in an argon atmosphere, 20 - 25 mg of the phosphorus sulfide composition was weighed and placed in an aluminum pan as a sample. Then, under the environmental conditions of a starting temperature of 25°C, a measurement temperature range of 30 - 350°C, a heating rate of 5°C / min, and 100 mL of argon per minute, differential scanning calorimetry was performed on this sample using a differential scanning calorimeter (DSC6300, manufactured by Seiko Instruments Inc.). Based on the obtained DSC curve, the heat of fusion (J / g) of the endothermic peak in the temperature range of 280°C or higher and 300°C or lower was calculated.

[0370] The heat of fusion of the above endothermic peak was calculated by determining the area enclosed by the endothermic melting curve including the endothermic peak and the baseline. The baseline in the endothermic peak was set as the line connecting Figure 5 the points R and S shown.

[0371] [2] [Manufacture of Sulfide - based Inorganic Solid Electrolyte Material]

[0372] <Example 1>

[0373] (Manufacture of Li 10 P3S 12 )

[0374] In an argon atmosphere at 20°C, 1.27 g of powdery phosphorus sulfide composition 1 (manufactured by Perimeter Solutions, product name: Normal / S, lot number: 22D1218453), 0.79 g of Li2S (manufactured by Furukawa Machinery Metal Co., Ltd., purity 99.9%), and 0.04 g of Li3N (manufactured by Furukawa Machinery Metal Co., Ltd.) were weighed.

[0375] Then, in an argon environment at 20 °C, the weighed phosphorus sulfide composition 1, Li2S, and Li3N were ground and mixed using a mortar to obtain a mixture (a1).

[0376] In an argon environment at 20 °C, 2.1 g of the obtained mixture (a1) was mechanically chemically treated using a planetary ball mill (45 mL zirconia container, using 18 zirconia balls with a diameter of 10 mm) to obtain a material (b1). More specifically, after mechanically grinding the mixture (a1) at 400 rpm for 10 minutes, it was left standing for 5 minutes, and this treatment was carried out for 120 cycles to obtain the material (b1). During the mechanical grinding, after 15 hours from the start of the mechanochemical treatment, the powder adhering to the wall surface of the zirconia container and the surface of the zirconia balls was scraped off.

[0377] The obtained material (b1) was placed in a carbon crucible and heat-treated using a heating furnace in an argon environment at 270 °C for 2 hours to obtain a sulfide-based inorganic solid electrolyte material represented by Li 10 P3S 12 represented sulfide-based inorganic solid electrolyte material.

[0378] (Manufacture of Li3PS4)

[0379] In an argon environment at 20 °C, 1.3 g of powdery phosphorus sulfide composition 1 (manufactured by Perimeter Solutions, product name: Normal / S, lot number: 22D1218453) and 0.8 g of Li2S (manufactured by Furukawa Machinery Metal Co., Ltd., purity 99.9%) were weighed.

[0380] Then, in an argon environment at 20 °C, the weighed phosphorus sulfide composition 1 and Li2S were ground and mixed using a mortar to obtain a mixture (a2).

[0381] In an argon environment at 20 °C, 2.1 g of the obtained mixture (a2) was mechanically chemically treated using a planetary ball mill (45 mL zirconia container, using 18 zirconia balls with a diameter of 10 mm) to obtain a material (b2). More specifically, after mechanically grinding the mixture (a2) at 400 rpm for 10 minutes, it was left standing for 5 minutes, and this treatment was carried out for 120 cycles to obtain the material (b2). During the mechanical grinding, after 15 hours from the start of the mechanochemical treatment, the powder adhering to the wall surface of the zirconia container and the surface of the zirconia balls was scraped off.

[0382] The obtained material (b2) was placed in a carbon crucible and heat-treated using a heating furnace in an argon environment at 270 °C for 2 hours to obtain a sulfide-based inorganic solid electrolyte material represented by Li3PS4.

[0383] <Example 2>

[0384] Except for using the powdery phosphorus sulfide composition 2 (manufactured by Kanto Chemical Co., Inc., Deer 1 grade, lot number: 607H1801) instead of the phosphorus sulfide composition 1, the same procedure as in Example 1 was carried out, and sulfide-based inorganic solid electrolyte materials represented by Li 10 P3S 12 and sulfide-based inorganic solid electrolyte materials represented by Li3PS4 were obtained respectively.

[0385] <Comparative Example 1>

[0386] 50 g of the powdery phosphorus sulfide composition 1 (manufactured by Perimeter Solutions, product name: Normal / S, lot number: 22D1218453) was placed in a quartz container and set in a vacuum heating device (manufactured by Furukawa Machinery Metal Co., Ltd.), and heated at 300 °C for 2 hours under a reduced pressure condition of -0.094 MPa.

[0387] Then, the valves of each part were closed, and the quartz container heated to 300 °C was immersed in a bucket filled with water while maintaining the vacuum, and rapidly cooled to 30 °C. The component accumulated at the bottom of the quartz container cooled to 30 °C was designated as "phosphorus sulfide composition 3".

[0388] Then, except for using the phosphorus sulfide composition 3 instead of the phosphorus sulfide composition 1, the same procedure as in Example 1 was carried out, and sulfide-based inorganic solid electrolyte materials represented by Li 10 P3S 12 and sulfide-based inorganic solid electrolyte materials represented by Li3PS4 were obtained respectively.

[0389] <Comparative Example 2>

[0390] Except for using the powdery phosphorus sulfide composition 4 (manufactured by Perimeter Solutions, product name: Normal / eXG, lot number: 22D1222095) instead of the phosphorus sulfide composition 1, the same procedure as in Example 1 was carried out, and sulfide-based inorganic solid electrolyte materials represented by Li 10 P3S 12 and sulfide-based inorganic solid electrolyte materials represented by Li3PS4 were obtained respectively.

[0391] Table 1

[0392]

[0393] Compared with the sulfide-based inorganic solid electrolyte materials of the comparative examples, the lithium ion conductivity of the sulfide-based inorganic solid electrolyte materials of the examples was improved.

[0394] This application claims priority based on Japanese Patent Application No. 2022-181107, Japanese Patent Application No. 2022-181108, and Japanese Patent Application No. 2022-181109 filed on November 11, 2022, and the entire contents of the Japanese patent application are incorporated herein by reference.

[0395] Description of Reference Numerals

[0396] 100: Lithium-ion battery.

[0397] 101: Positive electrode active material layer.

[0398] 103: Negative electrode active material layer.

[0399] 105: Current collector.

[0400] 110: Positive electrode.

[0401] 120: Electrolyte layer.

[0402] 130: Negative electrode.

Claims

1. A method for manufacturing a sulfide-based inorganic solid electrolyte material, wherein, the method for manufacturing the sulfide-based inorganic solid electrolyte material includes a step of obtaining a glassy sulfide-based inorganic solid electrolyte material by subjecting a raw material composition of the sulfide-based inorganic solid electrolyte material containing a lithium sulfide and a phosphorus sulfide composition to mechanical treatment to cause a chemical reaction among the components while vitrifying, the phosphorus sulfide composition has three or more peaks in the range of 2θ = 22.5° or more and 24.5° or less in the X-ray diffraction analysis spectrum obtained by the method described in the following X-ray diffraction analysis, X-ray diffraction analysis: Using an X-ray diffractometer, under the conditions of a voltage of 40 kV, a current of 40 mA, a divergence slit of 1°, a longitudinal limit of the divergence slit of 10 mm, a scattering slit of 1°, a receiving slit of 0.3 mm, a measurement start angle of 3°, a measurement end angle of 90°, and a scanning speed of 0.2° / min, using CuKα rays as the radiation source, the phosphorus sulfide composition is placed in an airtight sample holder filled with argon, and the X-ray diffraction analysis spectrum of the phosphorus sulfide composition is obtained.

2. The method for manufacturing a sulfide-based inorganic solid electrolyte material according to claim 1, wherein, the phosphorus sulfide composition contains P2S5.

3. The method for manufacturing a sulfide-based inorganic solid electrolyte material according to claim 2, wherein, the content of P2S5 in the phosphorus sulfide composition is 20% by mass or more.

4. The method for manufacturing a sulfide-based inorganic solid electrolyte material according to any one of claims 1 to 3, wherein, the phosphorus sulfide composition is in powder form.

5. The method for manufacturing a sulfide-based inorganic solid electrolyte material according to any one of claims 1 to 4, wherein, the mechanical treatment includes mechanochemical treatment.

6. The method for manufacturing a sulfide-based inorganic solid electrolyte material according to any one of claims 1 to 5, wherein, the method for manufacturing the sulfide-based inorganic solid electrolyte material further includes a step of heat-treating the glassy sulfide-based inorganic solid electrolyte material in the range of 180°C or more and 500°C or less.

7. The method for manufacturing a sulfide-based inorganic solid electrolyte material according to any one of claims 1 to 6, wherein, The lithium ion conductivity of the sulfide-based inorganic solid electrolyte material measured by the method described in the following measurement of lithium ion conductivity is 1.0×10 -3 S / cm or more, Measurement of lithium ion conductivity: First, 110 mg of the sulfide-based inorganic solid electrolyte material is pressurized under the conditions of 270 MPa and 10 minutes to obtain a disk-shaped sample with a diameter of 9.5 mm and a thickness of 1 mm. Then, using an electrochemical measurement device, under the conditions of an applied voltage of 10 mV, a measurement frequency range of 0.1 Hz to 3 MHz, and a measurement temperature of 27°C, using a Li foil as the electrode, the lithium ion conductivity of the obtained disk-shaped sample is measured by the alternating current impedance method.

8. A sulfide-based inorganic solid electrolyte material, wherein, the sulfide-based inorganic solid electrolyte material is a sulfide-based inorganic solid electrolyte material obtained by the method for manufacturing a sulfide-based inorganic solid electrolyte material according to any one of claims 1 to 7.

9. A method for manufacturing a phosphorus sulfide composition, wherein, the method for manufacturing the phosphorus sulfide composition includes a step of sorting a phosphorus sulfide composition having three or more peaks in the range of 2θ = 22.5° or more and 24.5° or less in the X-ray diffraction analysis spectrum obtained by the method described in the following X-ray diffraction analysis, X-ray diffraction analysis: Using an X-ray diffractometer, under the conditions of a voltage of 40 kV, a current of 40 mA, a divergence slit of 1°, a longitudinal limit of the divergence slit of 10 mm, a scattering slit of 1°, a receiving slit of 0.3 mm, a measurement start angle of 3°, a measurement end angle of 90°, and a scanning speed of 0.2° / minute, using CuKα rays as the radiation source, the phosphorus sulfide composition is placed in an airtight sample holder filled with argon to obtain the X-ray diffraction analysis spectrum of the phosphorus sulfide composition.

10. The method for manufacturing a phosphorus sulfide composition according to claim 9, wherein, the phosphorus sulfide composition contains P2S5.

11. The method for manufacturing a phosphorus sulfide composition according to claim 10, wherein, the content of P2S5 in the phosphorus sulfide composition is 20% by mass or more.

12. The method for manufacturing a phosphorus sulfide composition according to any one of claims 9 to 11, wherein, the phosphorus sulfide composition is in powder form.

13. A method for manufacturing a sulfide-based inorganic solid electrolyte material, wherein, the method for manufacturing the sulfide-based inorganic solid electrolyte material includes: a step of obtaining a phosphorus sulfide composition by using the method for manufacturing a phosphorus sulfide composition according to any one of claims 9 to 12; and a step of subjecting a raw material composition of a sulfide-based inorganic solid electrolyte material containing lithium sulfide and the phosphorus sulfide composition to mechanical treatment to cause a chemical reaction among the components while vitrifying to obtain a glassy sulfide-based inorganic solid electrolyte material.

14. The method for manufacturing a sulfide-based inorganic solid electrolyte material according to claim 13, wherein, the mechanical treatment includes mechanochemical treatment.

15. The method for manufacturing a sulfide-based inorganic solid electrolyte material according to claim 13 or 14, wherein, the method for manufacturing the sulfide-based inorganic solid electrolyte material further includes a step of heat-treating the glassy sulfide-based inorganic solid electrolyte material in the range of 180°C or more and 500°C or less.

16. The method for manufacturing a sulfide-based inorganic solid electrolyte material according to any one of claims 13 to 15, wherein, The lithium ion conductivity of the sulfide-based inorganic solid electrolyte material measured by the method described in the following measurement of lithium ion conductivity is 1.0×10 -3 S / cm or more, Measurement of lithium ion conductivity: First, a 110 mg sulfide-based inorganic solid electrolyte material is pressurized under the conditions of 270 MPa and 10 minutes to obtain a disk-shaped sample having a diameter of 9.5 mm and a thickness of 1 mm. Then, using an electrochemical measurement device, under the conditions of applying a voltage of 10 mV, a measurement frequency range of 0.1 Hz to 3 MHz, and a measurement temperature of 27°C, using a Li foil as the electrode, the lithium ion conductivity of the obtained disk-shaped sample is measured by the alternating current impedance method.

17. A sulfide-based inorganic solid electrolyte material, wherein, The sulfide-based inorganic solid electrolyte material is a sulfide-based inorganic solid electrolyte material obtained by the manufacturing method of the sulfide-based inorganic solid electrolyte material described in any one of claims 13 to 16.

18. An evaluation method for a phosphorus sulfide composition, wherein, the evaluation method for the phosphorus sulfide composition includes a step of determining that a phosphorus sulfide composition having three or more peaks in the range of 2θ = 22.5° or more and 24.5° or less in the X-ray diffraction analysis spectrum obtained by the method described in the following X-ray diffraction analysis is qualified, X-ray diffraction analysis: Using an X-ray diffractometer, under the conditions of a voltage of 40 kV, a current of 40 mA, a divergence slit of 1°, a longitudinal limit of the divergence slit of 10 mm, a scattering slit of 1°, a receiving slit of 0.3 mm, a measurement start angle of 3°, a measurement end angle of 90°, and a scanning speed of 0.2° / minute, using CuKα rays as the radiation source, the phosphorus sulfide composition is placed in an airtight sample holder filled with argon to obtain the X-ray diffraction analysis spectrum of the phosphorus sulfide composition.

19. The evaluation method for a phosphorus sulfide composition according to claim 18, wherein, the phosphorus sulfide composition contains P2S5.

20. The evaluation method for a phosphorus sulfide composition according to claim 19, wherein, the content of P2S5 in the phosphorus sulfide composition is 20% by mass or more.

21. The evaluation method for a phosphorus sulfide composition according to any one of claims 18 to 20, wherein, the phosphorus sulfide composition is in powder form.

22. A phosphorus sulfide composition, which is a phosphorus sulfide composition for a sulfide-based inorganic solid electrolyte material containing at least P2S5 and P4S9, wherein, when the total content of P2S5, P4S9, P4S7, and P4S3 in the phosphorus sulfide composition is set to 100% by mass, Based on the solid 31 The content of the P2S5 calculated from the P-NMR spectrum is 30% by mass or more and 60% by mass or less, the crystallinity calculated from the spectrum obtained by X-ray diffraction using CuKα rays as the radiation source is 40% or more and 70% or less.

23. The phosphorus sulfide composition according to claim 22, wherein, Based on the solid 31 The content of P4S9 calculated from the 31P-NMR spectrum is 40% by mass or more and 70% by mass or less.

24. The phosphorus sulfide composition according to claim 22 or 23, wherein, the total content of P2S5 and P4S9 is 90% by mass or more.

25. The phosphorus sulfide composition according to any one of claims 22 to 24, wherein, in the differential scanning calorimetry curve of the phosphorus sulfide composition obtained by differential scanning calorimetry measurement, an endothermic peak is observed in the temperature range of 280°C or more and 300°C or less, and the melting heat of the endothermic peak is 60 J / g or more and 90 J / g or less.

26. The phosphorus sulfide composition according to any one of claims 22 to 25, wherein, the phosphorus sulfide composition is in powder form.

27. A raw material composition for a sulfide-based inorganic solid electrolyte material, wherein, the raw material composition for a sulfide-based inorganic solid electrolyte material contains the phosphorus sulfide composition described in any one of claims 22 to 26 and lithium sulfide.

28. A manufacturing method for a sulfide-based inorganic solid electrolyte material, wherein, The manufacturing method of the sulfide-based inorganic solid electrolyte material includes a step of mechanically treating the raw material composition of the sulfide-based inorganic solid electrolyte material described in claim 27.

29. A sulfide-based inorganic solid electrolyte material, wherein, the sulfide-based inorganic solid electrolyte material contains a mechanically treated product of the raw material composition of the sulfide-based inorganic solid electrolyte material described in claim 27.

30. A sulfide-based inorganic solid electrolyte, wherein, the sulfide-based inorganic solid electrolyte contains the sulfide-based inorganic solid electrolyte material described in any one of claims 8, 17, and 29.

31. A sulfide-based inorganic solid electrolyte membrane, wherein, the sulfide-based inorganic solid electrolyte membrane contains, as a main component, the sulfide-based inorganic solid electrolyte described in claim 30.

32. A lithium ion battery, which is a lithium ion battery including a positive electrode having a positive electrode active material layer, an electrolyte layer, and a negative electrode having a negative electrode active material layer, wherein, at least one of the positive electrode active material layer, the electrolyte layer, and the negative electrode active material layer contains the sulfide-based inorganic solid electrolyte material described in any one of claims 8, 17, and 29.

Citation Information

Patent Citations

  • Sulfide solid electrolytic material, battery, and method for manufacturing sulfide solid electrolytic material

    JP2016027545A

  • Power storage device and separator for power storage device

    JP2022181107A

  • Information input device, information input program, and storage medium

    JP2022181108A

  • Interference length variable silencer

    JP2022181109A